Method for producing recycled water-absorbing resin

JP2025021171APending Publication Date: 2025-02-13NIPPON SHOKUBAI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023124933
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13

AI Technical Summary

Benefits of technology

【0015】 本発明の一態様によれば、使用済み吸収性物品から、加圧下吸水倍率が十分回復している、リサイクル吸水性樹脂を効率よく製造できるとの効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021171000001
    Figure 2025021171000001
  • Figure 2025021171000002
    Figure 2025021171000002
  • Figure 2025021171000003
    Figure 2025021171000003
Patent Text Reader

Abstract

To provide a method for efficiently producing a recycled water-absorbing resin which has a sufficiently recovered water absorption magnitude under pressure from a used absorptive article.SOLUTION: A method for producing a recycled water-absorbing resin includes a surface crosslinking treatment step of forming a crosslinked layer by a surface crosslinking agent on the surface of a recycled water absorptive resin having a 5-minute water soluble component amount of 5 mass% or less, and a 16-hour water-soluble component amount of 10 mass% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a recycled water-absorbent resin. More specifically, the present invention relates to a method for producing a recycled water-absorbent resin from a water-absorbent resin contained in a used absorbent article. [Background technology]

[0002] Super absorbent polymers (SAP) are water-swellable, water-insoluble polymer gelling agents that are used in a variety of absorbent products, including disposable diapers, sanitary napkins, adult incontinence products (incontinence pads), hygiene materials (sanitary products) such as pet sheets, soil water retention agents for agricultural and horticultural use, and industrial water-stopping agents.

[0003] Among these, the main applications of water-absorbent resins are sanitary materials such as disposable diapers and sanitary napkins. After being used for a short period of time (at most about one day), these sanitary materials are discarded in large quantities as used absorbent articles and incinerated.

[0004] In recent years, attempts have been made to recycle such used absorbent articles from the viewpoint of environmental protection, etc. For example, sanitary materials contain raw materials such as pulp, nonwoven fabric, adhesives, etc. in addition to the above-mentioned water-absorbent resin, and material recycling has been attempted in which these raw materials are separated from used sanitary materials and reused.

[0005] Patent Document 1 discloses a method for recycling a water-absorbent resin, which comprises separating the water-absorbent resin from a used absorbent article and subjecting the extracted water-absorbent resin to a washing and dehydration treatment. Patent Document 1 also discloses that the water-absorbent resin to be recycled is subjected to a surface cross-linking treatment after the above-mentioned washing and dehydration treatment, thereby improving (regenerating) the water-absorbency performance, such as the water-absorbency capacity under pressure, of the water-absorbent resin to be recycled.

[0006] Patent Document 2 discloses a method for recovering water absorbing ability by contacting a water-absorbent resin separated from a used absorbent article with a polyvalent metal salt, dehydrating the resin, and then contacting the resin with a complex-forming compound that forms a complex with a metal contained in the polyvalent metal salt.

[0007] Patent Document 3 discloses a method for dehydrating and separating the water-absorbent polymer by adding a transition metal salt and, optionally, an alkali metal salt or an alkaline earth metal salt to a mixture of a pulp component and a water-absorbent polymer obtained from a used absorbent article. Patent Document 3 also discloses a method for recovering the water-absorbency of the water-absorbent polymer by washing the separated water-absorbent polymer and then treating it with an alkali.

[0008] Patent Document 4 discloses a method for recycling a water-absorbent resin, in which the water-absorbent resin removed from a used absorbent article is treated with an acid and then with an alkali metal ion source. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2003-326161 A [Patent Document 2] International Publication WO2021 / 162082 Brochure [Patent Document 3] JP 2003-225645 A [Patent Document 4] JP 2019-135046 A Summary of the Invention [Problem to be solved by the invention]

[0010] However, the water absorbent resin recycling methods described in Patent Documents 2 to 4 have a problem that the water absorbency under pressure of the recycled water absorbent resin is not sufficiently restored. Also, in the recycling method described in Patent Document 1 in which the washing and dehydration treatment are followed by the surface cross-linking treatment, the water absorbency under pressure of the recycled water absorbent resin may not be restored.

[0011] Furthermore, Patent Document 1 discloses that the water absorbent resin recycled by the method described in Patent Document 1 has a significantly low amount of water-soluble components (16-hour water-soluble component amount) measured by stirring in deionized water for 16 hours. Here, in the water absorbent resin contained in the used absorbent article, in addition to the water-soluble components generated when producing a fresh water absorbent resin, some polymer components in the water absorbent resin are changed to water-soluble components due to deterioration and cleavage of bonds and / or crosslinked structures constituting the water absorbent resin by "absorbed liquid such as human waste" absorbed by the water absorbent resin during or after use. Therefore, the water absorbent resin contained in the used absorbent article contains a predetermined amount of water-soluble components. Therefore, the fact that the 16-hour water-soluble component amount is significantly low means that almost all of the predetermined amount of water-soluble components is removed by washing and dehydration treatment in the recycling process. From the above, the method described in Patent Document 1 has a problem in that a part of polymer components constituting a water absorbent resin contained in a used absorbent article is removed, and as a result, the amount of water absorbent resin finally recycled is reduced, and the production efficiency of the recycled water absorbent resin is reduced.

[0012] An object of the present invention is to solve the above-mentioned problems and to provide a method for efficiently producing a recycled water-absorbent resin in which the absorbency under pressure has been sufficiently restored from used absorbent articles. [Means for solving the problem]

[0013] As a result of intensive research, the present inventors have found that in order to sufficiently improve the water absorption capacity under pressure of a water absorbent resin by surface cross-linking treatment, it is necessary that the water-soluble components present on the surface (surface layer) of the water absorbent resin to be subjected to surface cross-linking treatment are small. Based on this, the present inventors have found that the above-mentioned problem can be solved by performing surface cross-linking treatment after reducing (removing) the water-soluble components, particularly on the surface portion, while reducing the total amount of water-soluble components removed from the water absorbent resin contained in a used absorbent article, even if the total amount of water-soluble components is not reduced so much, and have arrived at the present invention.

[0014] One embodiment of the present invention relates to a method for producing a recycled water absorbent resin, comprising a surface cross-linking treatment step of forming a cross-linked layer by a surface cross-linking agent on a surface of a recovered water absorbent resin recovered from used absorbent articles to obtain a reusable water absorbent resin, wherein the recovered water absorbent resin has a 5-minute water soluble component amount of 5 mass% or less and a 16-hour water soluble component amount of 10 mass% or more relative to the total mass of the recovered water absorbent resin. Effect of the Invention

[0015] According to one aspect of the present invention, an effect is exhibited in that a recycled water-absorbent resin in which the absorbency under pressure has been sufficiently restored can be efficiently produced from used absorbent articles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited thereto, and various modifications are possible within the scope described, and the technical scope of the present invention also includes embodiments obtained by appropriately combining the technical means disclosed in the different embodiments. Note that "acid (salt)" means "acid and / or its salt," and "(meth)acrylic" means "acrylic and / or methacrylic." Furthermore, the mass of the water-absorbent resin is expressed as a value converted into a solid content unless otherwise specified.

[0017] In this specification, "EDANA" is an abbreviation for European Disposables and Nonwovens Associations. Also, "ERT" is an abbreviation for EDANA Recommended Test Methods, a European standard (almost a global standard) for measuring water-absorbent resins. In one embodiment of the present invention, unless otherwise specified, the physical properties of the water-absorbent resin are measured in accordance with the original ERT (revised in 2002 / publicly known document).

[0018] 1. Technical Concept of the Present Invention The absorbent resin contained in a used absorbent article (hereinafter referred to as "used absorbent resin") has lower absorbency performance such as absorbency without pressure and absorbency under pressure, compared with the absorbent resin contained in an absorbent article before use (hereinafter referred to as "used absorbent resin"). Here, it is considered that the cause of the absorbency under pressure of the used absorbent resin is the collapse of the crosslinked structure of the surface of the absorbent resin before use due to water absorption during use, etc. Therefore, it is considered that the crosslinked structure of the surface is repaired by performing the surface crosslinking treatment described in Patent Document 1, etc., and as a result, the absorbency under pressure is restored.

[0019] However, during use, the bonds constituting the water absorbent resin are dissociated, the crosslinked structure is destroyed, and so on, so that some of the polymer components in the used water absorbent resin become water soluble components. In addition, the water soluble components do not function as crosslinking points in surface crosslinking. Therefore, when a large amount of water soluble components that do not function as crosslinking points are present on the surface of the used water absorbent resin, the crosslinked structure of the surface is not sufficiently repaired in the surface crosslinking treatment, and the recovery of the water absorption capacity under pressure is also insufficient.

[0020] In the examples of Patent Document 1, the water absorbent resin subjected to the surface cross-linking treatment is a water absorbent resin obtained by removing most of the water-soluble components from the entire used water absorbent resin by washing and dehydration treatment, and naturally, most of the water-soluble components on the surface are also removed. As a result, in the examples of Patent Document 1, the cross-linked structure on the surface of the used water absorbent resin is sufficiently restored by the surface cross-linking treatment, and it is considered that the water absorbent resin with the absorbency against pressure sufficiently restored was recycled.

[0021] On the other hand, in the examples of Patent Document 1, most of the water-soluble components in the entire water absorbent resin, including not only the surface but also the inside, have been removed from the water absorbent resin that has been subjected to the surface cross-linking treatment. As a result, the amount of the water absorbent resin to be recycled is reduced by removing a part of the components constituting the used water absorbent resin.

[0022] The object of the present invention is to efficiently produce a recycled water-absorbing resin having a sufficiently high recovery rate of water absorption capacity under pressure from a used absorbent article. Based on the above, the present inventors have found that the above object can be achieved by surface-crosslinking a water-absorbing resin from which water-soluble components present on the surface have been preferentially removed and which is recovered from a used absorbent article. The present inventors have also found that the amount of water-soluble components measured by a conventional method for measuring the amount of water-soluble components (e.g., "amount of water-soluble components for 16 hours") evaluates the amount of water-soluble components in the entire water-absorbing resin. Furthermore, the present inventors have found that the amount of water-soluble components present on the surface of a water-absorbing resin can be evaluated by the amount of water-soluble components measured by changing the stirring time to a shorter time, for example, 5 minutes, than the conventional method for measuring the amount of water-soluble components ("amount of water-soluble components for 5 minutes"). From these matters, the present inventors have found a technical idea that the above-mentioned problems can be solved by performing a surface cross-linking treatment on a recovered water absorbent resin recovered from a used absorbent article, which has a relatively large "16-hour water soluble component amount" and a small "5-minute water soluble component amount." Then, the present inventors have arrived at the present invention based on the above-mentioned technical idea.

[0023] 2. Method for producing recycled water-absorbent resin of the present invention A method for producing a recycled water absorbent resin according to one embodiment of the present invention (hereinafter, also referred to as "the method for producing a recycled water absorbent resin of the present invention") includes a surface cross-linking treatment step of forming a cross-linked layer by a surface cross-linking agent on a surface of a recovered water absorbent resin recovered from a used absorbent article to obtain a reusable water absorbent resin, and the recovered water absorbent resin has a 5-minute water-soluble component amount of 5 mass% or less and a 16-hour water-soluble component amount of 10 mass% or more relative to the total mass of the recovered water absorbent resin.

[0024] In the "recovered water absorbent resin" in the method for producing a recycled water absorbent resin of the present invention, the amount of 5-minute water soluble components is 5% by mass or less and the amount of 16-hour water soluble components is 10% by mass or more, based on the total mass of the recovered water absorbent resin. As described in the above section of <Technical Concept of the Present Invention>, the amount of the 5-minute water soluble components in the "recovered water absorbent resin" is as small as 5% by mass or less, and therefore the amount of water soluble components present on the surface is small. Therefore, in the surface cross-linking treatment step in the method for producing a recycled water absorbent resin of the present invention, a water absorbent resin in which the cross-linked structure on the surface is sufficiently restored and the water absorption capacity under pressure is sufficiently restored can be obtained. In addition, since the amount of the 16-hour water soluble components in the "recovered water absorbent resin" is as large as 10% by mass or more, the amount of components removed as water soluble components before the surface cross-linking treatment is small among the components constituting the used water absorbent resin in the recycling method of the present invention. Therefore, the amount of the water absorbent resin recycled by the recycling method of the present invention is increased. From the above, the method for producing a recycled water absorbent resin of the present invention has the effect of efficiently producing a recycled water absorbent resin whose absorbency under pressure has been sufficiently restored from used absorbent articles.

[0025] [2-1. Absorbent articles] An "absorbent article" is an article used for absorbing water. More specifically, an "absorbent article" is, for example, an absorbent article including an absorbent body containing a water-absorbent resin and a fibrous material, a top sheet having liquid permeability, and a back sheet having liquid impermeability. The absorbent body is suitably manufactured by blending a water-absorbent resin with a fibrous material, or by sandwiching a water-absorbent resin between fibrous materials and molding the mixture into a film, a tube, a sheet, or the like. Examples of the fibrous material include hydrophilic fibers such as ground wood pulp, cotton linters, crosslinked cellulose fibers, rayon, cotton, wool, acetate, vinylon, and the like.

[0026] In the manufacturing method of the recycled water absorbent resin of the present invention, the "used absorbent article" particularly includes used sanitary materials that have absorbed body fluids (liquids to be absorbed) such as urine, blood, etc. Examples of the sanitary materials include sanitary materials (sanitary products) such as paper diapers, sanitary napkins, adult incontinence products (incontinence pads), and pet sheets.

[0027] [2-2. Water-absorbing resin] The term "water-absorbent resin" refers to a water-swellable, water-insoluble polymer gelling agent, and is not particularly limited, but refers to a commonly used water-absorbent resin having a water-absorption capacity of 10 to 1000. More specifically, the water-absorbent resin before absorbing the liquid to be absorbed (hereinafter also referred to as "initial water-absorbent resin") preferably satisfies the physical property of a CRC of 5 g / g or more as specified in ERT441.2-02, as "water-swellability."

[0028] In one embodiment of the present invention, specific examples of the water-absorbent resin include polyacrylic acid (salt)-based resins, polysulfonic acid (salt)-based resins, maleic anhydride (salt)-based resins, polyacrylamide-based resins, polyvinyl alcohol-based resins, polyethylene oxide-based resins, polyaspartic acid (salt)-based resins, polyglutamic acid (salt)-based resins, polyalginic acid (salt)-based resins, starch-based resins, cellulose-based resins, (meth)acrylate crosslinked polymers, saponified crosslinked products of (meth)acrylate-vinyl acetate copolymers, starch-acrylate graft polymers and crosslinked products thereof.

[0029] [2-3. Recycled water-absorbent resin] In one embodiment of the present invention, the "recovered water absorbent resin" is a water absorbent resin derived from a used absorbent article and is subjected to the surface cross-linking treatment step. The "recovered water absorbent resin" has a 5-minute water soluble component amount of 5% by mass or less and a 16-hour water soluble component amount of 10% by mass or more, based on the total mass of the recovered water absorbent resin. In the method for producing a recycled water absorbent resin of the present invention, the method for subjecting the "recovered water absorbent resin" to the surface cross-linking treatment step is not particularly limited, and examples thereof include the following methods (a) to (c). (a) A water-absorbent resin derived from a used absorbent article and having a 5-minute water-soluble component amount of 5% by mass or less and a 16-hour water-soluble component amount of 10% by mass or more is separately obtained, and is subjected to the surface cross-linking treatment step as a "recovered water-absorbent resin". (b) A used water absorbent resin separated from a used absorbent article is separately obtained. Then, the used water absorbent resin is subjected to, for example, a washing step and / or a dehydration step described later, to prepare a "recovered water absorbent resin". Then, the prepared "recovered water absorbent resin" is subjected to the surface cross-linking step. (c) Separating the used water absorbent resin from the used absorbent article. Thereafter, the used water absorbent resin is subjected to, for example, a washing step and / or a dehydration step described later to prepare a "recovered water absorbent resin". Then, the prepared "recovered water absorbent resin" is subjected to the surface cross-linking step.

[0030] Therefore, when the "recovered water absorbent resin" is subjected to the surface cross-linking treatment step in the methods (b) and (c), the method for producing a recycled water absorbent resin of the present invention may further include carrying out a washing step described below and / or a dehydration step described below before the surface cross-linking treatment step. Also, when the "recovered water absorbent resin" is subjected to the surface cross-linking treatment step in the method (c), the method for producing a recycled water absorbent resin of the present invention may include a separation step described below.

[0031] The method for measuring the 5-minute water-soluble component amount and the 16-hour water-soluble component amount is not particularly limited, and they can be measured, for example, by the method shown in the Examples.

[0032] As described above, by making the 5-minute water-soluble content of the recovered water absorbent resin 5% by mass or less, the crosslinked structure of the surface is sufficiently restored in the surface crosslinking treatment step, and a reusable water absorbent resin having a sufficiently restored water absorption capacity under pressure can be obtained. From this viewpoint, the 5-minute water-soluble content of the recovered water absorbent resin is preferably 4% by mass or less, more preferably 3% by mass or less.

[0033] As described above, when the 16-hour water-soluble component amount of the recovered water absorbent resin is 10% by mass or more, the amount of reusable water absorbent resin and the amount of recycled water absorbent resin can be increased in the method for producing a recycled water absorbent resin of the present invention. From this viewpoint, the 16-hour water-soluble component amount of the recovered water absorbent resin is preferably 12% by mass or more, and more preferably 13% by mass or more.

[0034] [2-4. Reusable water-absorbing resin] In one embodiment of the present invention, the "reusable water absorbent resin" refers to a resin that is made reusable for applications requiring a water absorption function, which is a used water absorbent resin contained in a used absorbent article. Here, the used water absorbent resin contains liquid to be absorbed, such as human waste, and has been considered to have no other use than disposal. In other words, the "reusable water absorbent resin" is a water absorbent resin that is extracted from a used water absorbent article, and is a resin that is made reusable for the purpose of absorbing water, which is usually discarded, thermally recycled as fuel, or composted. In other words, the "reusable water absorbent resin" is a water absorbent resin whose absorption performance has been restored and which can be used for the purpose of absorbing water.

[0035] [2-5. Recycled water-absorbent resin] In one embodiment of the present invention, the water absorbent resin produced by the method for producing a recycled water absorbent resin of the present invention is defined as a "recycled water absorbent resin". The "recycled water absorbent resin" may be the "reusable water absorbent resin" itself, or may be a water absorbent resin produced using the "reusable water absorbent resin". The water absorbent resin produced using the "reusable water absorbent resin" may be, for example, a water absorbent resin containing the "reusable water absorbent resin", or a water absorbent resin produced using the "reusable water absorbent resin" as a part of a raw material.

[0036] [2-6. Surface cross-linking treatment process] The surface cross-linking step in the method for producing a recycled water absorbent resin of the present invention is a step of forming a cross-linked layer on the surface of the recovered water absorbent resin by a surface cross-linking agent to obtain a reusable water absorbent resin. Specifically, the surface cross-linking step is a step of providing a portion with high cross-link density on the surface layer of the recovered water absorbent resin (a portion several tens of μm from the surface of the recovered water absorbent resin), and is composed of a mixing step, a heat treatment step, and a cooling step (optional).

[0037] In the surface cross-linking treatment step, a surface-cross-linked water-absorbent resin (reusable water-absorbent resin) is obtained by radical cross-linking, surface polymerization, cross-linking reaction with a surface cross-linking agent, or the like on the surface of the recovered water-absorbent resin.

[0038] (Surface cross-linking agent) The surface crosslinking agent used in one embodiment of the present invention is not particularly limited. Examples of the surface crosslinking agent include organic or inorganic surface crosslinking agents. Among the organic or inorganic surface crosslinking agents, organic surface crosslinking agents that react with carboxyl groups are preferred from the viewpoints of the physical properties of the water-absorbent resin and the handling of the surface crosslinking agent. Examples of the organic surface crosslinking agent that reacts with carboxyl groups include one or more surface crosslinking agents disclosed in U.S. Patent No. 7,183,456. More specifically, examples of the organic surface crosslinking agent that reacts with carboxyl groups include polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyamine compounds or their condensates with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal salts, alkylene carbonate compounds, and cyclic urea compounds.

[0039] The amount of the surface crosslinking agent used is preferably 0.01 parts by mass or more and 10 parts by mass or less, more preferably 0.01 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the recovered water absorbent resin. When a mixture of multiple surface crosslinking agents is used as the surface crosslinking agent, the amount of the surface crosslinking agent used means the total amount of the multiple surface crosslinking agents used. The surface crosslinking agent is preferably added as an aqueous solution, and in this case, the amount of water used is preferably 0.1 parts by mass or more and 20 parts by mass or less, more preferably 0.5 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the recovered water absorbent resin. Furthermore, if necessary, a hydrophilic organic solvent can be used together with the surface crosslinking agent. In that case, the amount of the hydrophilic organic solvent used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the recovered water absorbent resin.

[0040] (Mixing process) The mixing step is a step of mixing the recovered water absorbent resin and the surface crosslinking agent. The method of mixing the recovered water absorbent resin and the surface crosslinking agent is not particularly limited. As a method of mixing the recovered water absorbent resin and the surface crosslinking agent, for example, a method of preparing a surface crosslinking agent solution in advance and mixing the surface crosslinking agent solution with the recovered water absorbent resin by preferably spraying or dropping the surface crosslinking agent solution onto the recovered water absorbent resin, more preferably by spraying the surface crosslinking agent solution onto the recovered water absorbent resin, can be mentioned.

[0041] The device for performing the mixing is not particularly limited, and the device for performing the mixing is preferably a high-speed stirring type mixer, more preferably a high-speed stirring type continuous mixer.

[0042] (Heat treatment process) The heat treatment step is a step of applying heat to the mixture obtained in the mixing step to cause a crosslinking reaction on the surface of the recovered water absorbent resin.

[0043] The device for causing the crosslinking reaction is not particularly limited. A preferred example of the device for causing the crosslinking reaction is a paddle dryer. The reaction temperature in the crosslinking reaction is appropriately set according to the type of surface crosslinking agent used. For example, the reaction temperature in the crosslinking reaction is preferably 50°C or more and 300°C or less, more preferably 100°C or more and 200°C or less.

[0044] When the cooling step is not carried out, the water-absorbent resin obtained in the heat treatment step is a reusable water-absorbent resin.

[0045] (cooling process) The cooling step is an optional step that is installed as necessary after the heat treatment step, and is a step of cooling the water-absorbent resin obtained in the heat treatment step and heated. The device that performs the cooling is not particularly limited. The device that performs the cooling is preferably a device with the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because the device used in the heat treatment step can be used as a cooling device by changing the heat medium in the device used in the heat treatment step to a refrigerant. The water-absorbent resin obtained in the heat treatment step is forcibly cooled, as necessary, to preferably 40°C or more and 80°C or less, more preferably 50°C or more and 70°C or less in the cooling step.

[0046] When the cooling step is carried out, the water-absorbent resin obtained in the cooling step becomes a reusable water-absorbent resin.

[0047] [2-7. Washing process, dehydration process] The method for producing a recycled water absorbent resin of the present invention may include carrying out a washing step described below and / or a dehydration step described below before the surface cross-linking treatment step. By carrying out the washing step and / or the dehydration treatment step, the recovered water absorbent resin can be prepared from the used water absorbent resin separated from the used absorbent article, and the prepared recovered water absorbent resin can be subjected to the surface cross-linking treatment step.

[0048] <Cleaning process> The washing step in the manufacturing method of the recycled water absorbent resin of the present invention is a step of washing the water absorbent resin with washing water. The water absorbent resin to be subjected to the washing step is not particularly limited as long as it is a water absorbent resin separated from a used absorbent article. The water absorbent resin to be subjected to the washing step may include, for example, a used water absorbent resin and a water absorbent resin after being dehydrated in a dehydration treatment step described later.

[0049] The washing step is specifically a step of removing water-soluble components in the water-absorbent resin with washing water. Specific methods include, for example, pouring washing water onto the swollen water-absorbent resin gel, immersing the swollen gel in washing water, and stirring the swollen gel while immersing it in washing water. In addition, in the washing step, at least a part of the substances absorbed in the water-absorbent resin, such as human waste components, may be removed together with the water-soluble components.

[0050] The washing water is not particularly limited as long as it can reduce the water-soluble components by the washing step compared to before the treatment and does not alter the water-absorbent resin. The washing water is preferably one that allows the water-absorbent resin to absorb water and swell. This is because the water-soluble components are easily removed when dehydrating the resin after it has absorbed water and swelled. Examples of such aqueous liquids include deionized water, tap water, distilled water, saline, and seawater. The aqueous liquid may also contain other components.

[0051] The cleaning water may be hot, ranging from room temperature to 100° C., or may be steam. When a hot aqueous liquid or a steam aqueous liquid is used as the cleaning water, not only a cleaning effect but also a sterilizing effect can be expected.

[0052] <Dehydration process> The dehydration process in the method for producing a recycled water absorbent resin of the present invention is a process for discharging the water-soluble component together with the absorbed component from the water absorbent resin. The water absorbent resin separated from the used absorbent article to be subjected to the dehydration process is not particularly limited as long as it is a water absorbent resin separated from the used absorbent article. The water absorbent resin separated from the used absorbent article to be subjected to the dehydration process may include, for example, a used water absorbent resin and a water absorbent resin after being washed in a washing process described below. The water absorbent resin to be subjected to the dehydration process is usually in a swollen gel state.

[0053] The dehydration process is, in detail, a process of discharging the absorbed liquid, which is present inside the absorbent resin and contains the water-soluble components, to the outside of the absorbent resin by shrinking the swollen gel of the absorbent resin. The absorbed liquid may contain other components besides the water-soluble components, and the other components are not particularly limited and may be, for example, human waste components. In addition, when the washing process is performed before the dehydration process, the washing water used in the washing process may also be included in the absorbed liquid.

[0054] The dehydration process in one embodiment of the present invention is not particularly limited as long as it is a process capable of reducing the water content of the swollen water-absorbent resin. The dehydration process may include contacting the water-absorbent resin separated from the used absorbent article with one or more selected from the group consisting of a polyvalent metal salt, an aqueous solution containing a polyvalent metal salt, an acidic liquid, a hydrophilic organic solvent, and an aqueous solution containing a hydrophilic organic solvent. Hereinafter, a chemical selected from the group consisting of a polyvalent metal salt, an aqueous solution containing a polyvalent metal salt, an acidic liquid, a hydrophilic organic solvent, and an aqueous solution containing a hydrophilic organic solvent that can be used in the dehydration process is also referred to as a "dehydration chemical". More specifically, the dehydration process may be carried out, for example, by a method of contacting a swollen gel of a water-absorbent resin with an aqueous solution containing a hydrophilic organic solvent; a method of contacting the swollen gel with an aqueous solution of a low pH (e.g., 3 or less); or a method of contacting the swollen gel with an aqueous solution of a polyvalent metal salt such as calcium chloride. Specific examples of contacting the swollen gel of the water-absorbent resin with these liquids include pouring the liquid onto the swollen gel, immersing the swollen gel in the liquid, stirring the swollen gel while immersing it in the liquid, etc. The dehydration treatment step can also be carried out by a method of applying a voltage to the swollen gel using a pair of electrodes.

[0055] In the case where a swollen gel of a water absorbent resin is immersed in an aqueous solution containing a hydrophilic organic solvent, the concentration of the hydrophilic organic solvent in the aqueous solution to be immersed is preferably 35% by mass or more, more preferably 40% by mass or more, and further preferably 45% by mass or more.

[0056] The hydrophilic organic solvent is an organic solvent having a solubility of 20 g or more in 100 mL of water at 20° C. More preferably, the solubility is 25 g or more in 100 mL of water at 20° C., and even more preferably, the solubility is 30 g or more in 100 mL of water at 20° C.

[0057] Examples of such hydrophilic organic solvents include (1) lower alcohols, such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, tert-butyl alcohol, etc., (2) ketones, such as acetone, methyl ethyl ketone, etc., (3) ethers, such as tetrahydrofuran, dioxane, etc., and (4) esters, such as methyl acetate, methyl lactate, ethyl lactate, etc. These hydrophilic organic solvents may be used alone or in combination of two or more kinds.

[0058] When the swollen gel of the water-absorbent resin is immersed in an aqueous solution with a low pH (for example, 3 or less), the pH of the aqueous solution is preferably 3 or less, and more preferably 0.5 to 2.5. In the aqueous solution, either an inorganic acid or an organic acid can be used as the acid. In the case of an inorganic acid, hydrochloric acid, sulfuric acid, etc. can be used. In the case of an organic acid, tartaric acid, glycolic acid, malic acid, citric acid, succinic acid, acetic acid, etc. can be used. These acids may be used alone or in combination of two or more.

[0059] In the case of contacting with an aqueous solution of a polyvalent metal salt, examples of the polyvalent metal salt include metal salts of calcium, magnesium, aluminum, iron, cobalt, nickel, and copper. These polyvalent metal salts may be used alone or in combination of two or more.

[0060] <Conditions etc.> In one embodiment of the present invention, only one of the washing step and the dehydration step may be performed, or both of the steps may be performed. When the manufacturing method for recycled water absorbent resin of the present invention includes both the washing step and the dehydration step, the order of performing each step is not limited. Also, the washing step and the dehydration step may each be performed multiple times. Specifically, for example, the manufacturing method for recycled water absorbent resin of the present invention may include performing the washing step on the water absorbent resin separated from a used absorbent article, and then performing the dehydration step to prepare a recovered water absorbent resin. Also, the manufacturing method for recycled water absorbent resin of the present invention may include performing the washing step, the dehydration step, the washing step, and the dehydration step in this order on the water absorbent resin separated from a used absorbent article, to prepare a recovered water absorbent resin. This is because the water-absorbing resin absorbs the wash water and further swells in the washing step, and when the absorbed liquid and water-soluble components are discharged in the subsequent dehydration step, a larger amount of water-soluble components can be discharged compared to the case where a simple dehydration step is performed.

[0061] In addition, in the case where the discharged water-soluble component adheres again to the surface of the water absorbent resin, by carrying out the washing step, the dehydration step, and the washing step in this order, the water-soluble component that has adhered to the surface of the water absorbent resin after the dehydration step can be washed away, which is a more preferable method.

[0062] By appropriately adjusting the conditions in the washing step and the dehydration step, the 5-minute water-soluble component amount and the 16-hour water-soluble component amount of the recovered water-absorbent resin obtained relative to the total mass of the recovered water-absorbent resin can be controlled within the above-mentioned preferred range. Examples of the conditions in the washing step include the type and amount of washing water used, and, in the case where the swollen gel is stirred while immersed in the washing water, the stirring time, etc. Examples of the conditions in the dehydration step include, in the case where the separated water-absorbent resin is contacted with the "dehydration chemical" to perform the dehydration step, the amount of the "dehydration chemical" used and the time for which the "dehydration chemical" is contacted with the target water-absorbent resin, etc. The preferred conditions in the washing step and the dehydration step may vary appropriately depending on the form of the separated water-absorbent resin to be treated, the method of the washing step and the dehydration step, the type of washing water, the type of the "dehydration chemical", etc.

[0063] For example, when an aqueous liquid having high solubility for the soluble component is used as the washing water, the amount of the 5-minute water-soluble component and the amount of the 16-hour water-soluble component relative to the total mass of the recovered water-absorbent resin obtained are both small. On the other hand, when an aqueous liquid having low solubility for the water-soluble component is used as the washing water, the amount of the 5-minute water-soluble component and the amount of the 16-hour water-soluble component relative to the total mass of the recovered water-absorbent resin obtained are both large. Examples of aqueous liquids having high solubility for the soluble component include deionized water, tap water, and distilled water. Examples of aqueous liquids having low solubility for the soluble component include physiological saline and seawater.

[0064] When the amount of washing water used is large, both the amount of 5-minute water-soluble component and the amount of 16-hour water-soluble component relative to the total mass of the recovered water absorbent resin obtained are small, but the amount of 5-minute water-soluble component is particularly likely to be affected. On the other hand, when the amount of washing water used is small, both the amount of 5-minute water-soluble component and the amount of 16-hour water-soluble component relative to the total mass of the recovered water absorbent resin obtained are large, but the amount of 16-hour water-soluble component is particularly likely to be affected. The amount of washing water used is, for example, preferably 2,000 parts by mass or more and 1,000,000 parts by mass or less, more preferably 10,000 parts by mass or more and 100,000 parts by mass or less, relative to 100 parts by mass of the water absorbent resin to be subjected to the washing step.

[0065] When the stirring time is long when the swollen gel is stirred while immersed in the washing water in the washing step, both the 5-minute water-soluble component amount and the 16-hour water-soluble component amount relative to the total mass of the recovered water-absorbent resin obtained are small, but the 16-hour water-soluble component amount is particularly likely to be affected. On the other hand, when the stirring time is short, both the 5-minute water-soluble component amount and the 16-hour water-soluble component amount relative to the total mass of the recovered water-absorbent resin obtained are large, but the 16-hour water-soluble component amount is particularly likely to be affected. The stirring time is, for example, preferably 5 minutes or more and 60 minutes or less, more preferably 10 minutes or more and 45 minutes or less, and even more preferably 15 minutes or more and 30 minutes or less.

[0066] When the amount of the "dehydration chemical" used is large, the amount of the 5-minute water-soluble component and the amount of the 16-hour water-soluble component of the recovered water absorbent resin relative to the total mass of the recovered water absorbent resin are both small. On the other hand, when the amount of the "dehydration chemical" used is small, the amount of the 5-minute water-soluble component and the amount of the 16-hour water-soluble component of the recovered water absorbent resin relative to the total mass of the recovered water absorbent resin are both large, but the amount of the 16-hour water-soluble component is particularly susceptible to influence. The amount of the "dehydration chemical" used is, for example, preferably 100 parts by mass or more and 5,000 parts by mass or less, more preferably 100 parts by mass or more and 2,000 parts by mass or less, and even more preferably 100 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass of the water absorbent resin to be subjected to the dehydration treatment process.

[0067] When the time for contacting the "dehydration chemical" with the target water absorbent resin is long, the amount of 5-minute water soluble component and the amount of 16-hour water soluble component of the recovered water absorbent resin relative to the total mass of the recovered water absorbent resin are both small. On the other hand, when the time for contacting the "dehydration chemical" with the target water absorbent resin is short, the amount of 5-minute water soluble component and the amount of 16-hour water soluble component of the recovered water absorbent resin relative to the total mass of the recovered water absorbent resin are both large. The time for contacting the "dehydration chemical" with the target water absorbent resin is, for example, preferably 5 minutes or more and 60 minutes or less, more preferably 10 minutes or more and 45 minutes or less, and even more preferably 15 minutes or more and 30 minutes or less.

[0068] In addition, for example, by the following method, (i) washing the human waste adhering to the surface while suppressing the water absorption into the water absorbent resin using a small amount or low water absorbency washing water such as physiological saline, (ii) discharging the absorbed liquid absorbed in the water absorbent resin while suppressing the discharge of excessive water soluble components by a small amount or short time dehydration treatment, and (iii) washing the water soluble components adhering to the surface of the water absorbent resin with washing water, it is possible to suitably reduce the amount of 5-minute water soluble components while keeping the amount of 16-hour water soluble components high relative to the total mass of the recovered water absorbent resin. As a result, it is possible to prepare a recovered water absorbent resin whose amounts of 5-minute water soluble components and 16-hour water soluble components are within the above-mentioned ranges.

[0069] [2-8. Drying process, crushing and classification process] The manufacturing method of the recycled water absorbent resin of the present invention may include carrying out a drying step described below and / or a pulverization and classification step described below before the surface cross-linking treatment step. When the drying step and the pulverization step are carried out, the order is not limited, and the pulverization step may be carried out after the drying step, or conversely, the drying step may be carried out after the pulverization step. In addition, each of the drying step and the pulverization step may be carried out multiple times. For example, in the manufacturing method of the recycled water absorbent resin of the present invention, after carrying out the drying step, the water absorbent resin dried in the drying step may be pulverized in the pulverization step, and then the water absorbent resin pulverized and classified in the pulverization and classification step may be dried again by carrying out the drying step.

[0070] <Drying process> The drying step in the method for producing a recycled water absorbent resin of the present invention is a step of drying the water absorbent resin to reduce its moisture content. The water absorbent resin to be subjected to the drying step is not particularly limited as long as it is a water absorbent resin separated from a used absorbent article. The water absorbent resin to be subjected to the washing step may include, for example, a used water absorbent resin, a water absorbent resin after being treated in the washing step and / or the dehydration treatment step, and a water absorbent resin after being pulverized in the pulverization step described below.

[0071] By carrying out the drying step, the resin solid content of the recovered water absorbent resin to be subjected to the surface cross-linking treatment step can be controlled within a desired range. The resin solid content can be calculated from the loss on drying (the change in mass when 1 g of the water absorbent resin is heated at 180°C for 3 hours). The resin solid content is, for example, preferably 80% by mass or more, more preferably 85% by mass or more and 99% by mass or less, even more preferably 90% by mass or more and 98% by mass or less, and particularly preferably 92% by mass or more and 97% by mass or less.

[0072] In the drying step, the method for drying the water-absorbent resin is not particularly limited, and a known drying method can be applied. Examples of the method for drying the water-absorbent resin include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, and high humidity drying using high-temperature water vapor. Among the above-mentioned drying methods, hot air drying is preferred from the viewpoint of drying efficiency, and band drying in which hot air drying is performed on a ventilation belt is more preferred. In addition, for example, heat drying using an oven can be applied as a method for drying the water-absorbent resin.

[0073] The drying temperature (temperature of hot air) in the hot air drying is preferably 120°C or more and 250°C or less, more preferably 150°C or more and 200°C or less, from the viewpoint of the color tone of the water absorbent resin, drying efficiency, etc. In addition, the drying conditions other than the drying temperature, such as the wind speed of the hot air and the drying time, may be appropriately set according to the water content, total mass, and target resin solid content of the water absorbent resin to be dried. When band drying is performed, the various conditions described in International Publication Nos. 2006 / 100300, 2011 / 025012, 2011 / 025013, 2011 / 111657, etc. are appropriately applied as drying conditions.

[0074] By setting the above-mentioned drying temperature, drying time, etc. within the above-mentioned ranges, it is possible to set the CRC (absorption capacity), Ext (amount of 16-hour water-soluble component) and color tone within desired ranges in the recovered water absorbent resin and the reusable water absorbent resin in the manufacturing method for the recycled water absorbent resin of the present invention.

[0075] <Crushing / classification process> The drying step in the manufacturing method of the recycled water absorbent resin of the present invention is a step of pulverizing and classifying the water absorbent resin to adjust its shape and size (particle diameter). The water absorbent resin to be subjected to the pulverizing and classifying step is not particularly limited as long as it is a water absorbent resin separated from a used absorbent article. The water absorbent resin to be subjected to the pulverizing and classifying step may include, for example, a used water absorbent resin, a water absorbent resin after being treated in the washing step and / or the dehydration treatment step, and a water absorbent resin after being dried in the drying step.

[0076] By carrying out the pulverization and classification process, the shape and size (particle diameter) of the recovered water absorbent resin to be subjected to the surface cross-linking process can be controlled within a desired range. As a result, the shape and size (particle diameter) of the reusable water absorbent resin and the recycled water absorbent resin can be controlled within a desired range. The particle size distribution of the recovered water absorbent resin is preferably such that the mass average particle diameter (D50) is 300 μm or more and 600 μm or less, and the proportion of particles less than 150 μm is preferably 5 mass% or less. The upper limit of the mass average particle diameter (D50) is more preferably 500 μm or less, even more preferably 450 μm or less, and particularly preferably 400 μm or less. The proportion of particles less than 150 μm is more preferably 4 mass% or less, even more preferably 3 mass% or less, and particularly preferably 2 mass% or less.

[0077] In the pulverization and classification step, the method for pulverizing the water-absorbent resin is not particularly limited, and a known pulverization method can be applied. As a method for pulverizing the water-absorbent resin, for example, a method using a vibration mill can be mentioned.

[0078] In the pulverization and classification step, the method for classifying the water-absorbent resin is not particularly limited, and a known classification method can be applied. For example, a method using a sieve with appropriate mesh size can be mentioned as a method for classifying the water-absorbent resin.

[0079] [2-9. Separation process] The method for producing a recycled water absorbent resin of the present invention may include carrying out a separation step of separating the used water absorbent resin from the used absorbent article. The separation step, in detail, refers to taking out the used water absorbent resin from gaps in the pulp, nonwoven fabric, etc. contained in the used absorbent article and dispersing it in a treatment liquid. The method for carrying out the separation step is not particularly limited as long as the used water absorbent resin can be separated from the used absorbent article, and a known method can be applied. As a method for carrying out the separation step, for example, a method of stirring a mixture of the treatment liquid and the used absorbent article can be mentioned. The water absorbent resin dispersed in the treatment liquid can be recovered by a conventional solid-liquid separation means for separating soluble and insoluble substances, for example, filtration, centrifugation, etc.

[0080] The treatment liquid is not particularly limited, and for example, a liquid corresponding to the cleaning liquid or the dehydration chemical can be used. Here, when the cleaning liquid is used as the treatment liquid, the separation step and the washing step can be performed in parallel. In that case, the used water absorbent resin is dispersed in the treatment liquid, i.e., the washing liquid, and then washed. Thereafter, the washed water absorbent resin can be recovered from the treatment liquid by the solid-liquid separation means. Furthermore, when a liquid corresponding to the dehydration chemical is used as the treatment liquid, the separation step and the dehydration treatment step can be performed in parallel. In that case, the used water absorbent resin is dispersed in the treatment liquid, i.e., the liquid corresponding to the dehydration chemical, and then dehydrated. Thereafter, the dehydrated water absorbent resin can be recovered from the treatment liquid by the solid-liquid separation means.

[0081] [2-10. Absorbent article crushing (cutting) process] The method for producing a recycled water absorbent resin of the present invention may include carrying out an absorbent article crushing (cutting) step of crushing (cutting) used absorbent articles into crushed materials (cut materials) before or in parallel with the separation step.

[0082] The method of crushing (cutting) the used absorbent article is not particularly limited, and examples thereof include a method of cutting using a cutting tool such as a cutter. By carrying out the crushing (cutting) step, it is possible to increase the contact opportunity between the water absorbent resin in the absorbent article and cleaning water, dehydration chemicals, etc., thereby improving the cleaning effect, dehydration effect, speed, etc. In addition, by carrying out the absorbent article crushing (cutting) step, it is possible to easily separate each component, such as the used water absorbent resin, pulp, nonwoven fabric, etc., from the used absorbent article.

[0083] [2-11. Sterilization / disinfection process] In the method for producing a recycled water absorbent resin of the present invention, a sterilization / disinfection step for sterilizing and / or disinfecting the water absorbent resin can be carried out in parallel with or after the washing step and / or the dehydration step and / or the absorbent article crushing (cutting) step.

[0084] As a method for sterilizing and / or disinfecting the water-absorbent resin, for example, a method of treating the water-absorbent resin with a disinfectant can be mentioned. The disinfectant is not particularly limited, and a known one can be used. For example, sodium hypochlorite aqueous solution, chlorine dioxide aqueous solution, ozone water, hydrogen peroxide water, electrolytic water (acidic electrolytic water), etc. can be mentioned. It is preferable to efficiently mix the water-absorbent resin and the disinfectant by carrying out the sterilization / disinfection in a tank having an agitator blade and by convection of the aqueous solution.

[0085] [2-12. CRC recovery rate] In the method for producing a recycled water absorbent resin of the present invention, the recovery rate of CRC represented by the following formula (1) is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. {CRC [g / g] of the reusable water-absorbent resin / CRC [g / g] of the water-absorbent resin contained in the absorbent article before use} × 100 (1) In one embodiment of the present invention, "CRC" represents the water absorption capacity without pressure. In detail, "CRC" is an abbreviation of Centrifuge Retention Capacity, and indicates the absorption capacity of a water absorbent resin for 0.90 mass% saline solution in 30 minutes without pressure. Therefore, the CRC recovery rate is a parameter representing an index of recovery of the water absorption performance (water absorption capacity) of a reusable water absorbent resin without pressure, compared with the water absorbent resin contained in an absorbent article before use. A high CRC recovery rate means that the water absorption performance (water absorption capacity) without pressure, which is reduced by use, is suitably recovered by the manufacturing method of the recycled water absorbent resin of the present invention.

[0086] The method for measuring CRC can be a known method and is not particularly limited. Specifically, the method for measuring CRC described in the Examples can be used.

[0087] [2-13. Recovery rate of AUL0.3] In the method for producing a recycled water absorbent resin of the present invention, the recovery rate of AUL0.3, represented by the following formula (2), is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. {AUL0.3[g / g] of the reusable water-absorbent resin / AUL0.3[g / g] of the water-absorbent resin contained in the absorbent article before use}×100 (2) In one embodiment of the present invention, "AUL0.3" represents the absorbency under a pressure of 0.3 psi. In detail, "AUL0.3" is an abbreviation for "Absorbency under Load" and indicates the absorbency (unit: g / g) of a water absorbent resin for a 0.90 mass% sodium chloride aqueous solution under a pressure of 0.3 psi. Therefore, the recovery rate of AUL0.3 is a parameter representing an index of recovery of the water absorption performance (absorption capacity) of a reusable water absorbent resin under pressure, compared with the water absorbent resin contained in an absorbent article before use. A high recovery rate of AUL0.3 means that the water absorption performance (absorption capacity) under pressure, which is reduced by use, is suitably recovered by the manufacturing method of the recycled water absorbent resin of the present invention.

[0088] The method for measuring AUL0.3 is not particularly limited and may be a known method. Specifically, the method for measuring AUL0.3 described in the Examples may be used.

[0089] [2-14. Recycling rate of recovered water absorbent resin] In the recycling method of the present invention, the recycling rate of the recovered water absorbent resin, represented by the following formula (3), is preferably 80% or more, more preferably 83% or more, and even more preferably 86% or more. Recycling rate (%) = 100 - (amount of 16-hour water-soluble component of water-absorbent resin before recovery operation - amount of 16-hour water-soluble component of recovered water-absorbent resin) (3) In the formula (3), the "recovery operation" is a process of preparing a recovered water-absorbing resin from a used absorbent article, such as the washing process and the dehydration process. Thus, specifically, the "water-absorbing resin before the recovery operation" in the formula (3) means the water-absorbing resin before the washing process and the dehydration process. More specifically, the "water-absorbing resin before the recovery operation" may be, for example, a water-absorbing resin obtained by separating the water-absorbing resin from a used absorbent article by a method that does not substantially change the amount of the water-absorbing resin contained in the used absorbent article and the water-soluble component in the water-absorbing resin. That is, the "16-hour water-soluble component amount of the water-absorbing resin before the recovery operation" means the "16-hour water-soluble component amount of the used water-absorbing resin".

[0090] The fact that the recycling rate of the recovered water absorbent resin is a high value of 80% or more means that the amount of the components removed as water-soluble components before the surface cross-linking treatment is small among the components constituting the used water absorbent resin. Therefore, in this case, the amount of the water absorbent resin recycled can be increased by the recycling method of the present invention.

[0091] The method for measuring the recycling rate of the recovered water absorbent resin may be a known method and is not particularly limited. Specifically, the method for measuring the recycling rate of the recovered water absorbent resin may be the measurement method described in the Examples.

[0092] [2-15. Recycled water absorbent resin manufacturing process] The method for producing a recycled water absorbent resin of the present invention may include a recycled water absorbent resin production step of producing a recycled water absorbent resin using a reusable water absorbent resin. In the method for producing a recycled water absorbent resin of the present invention that does not include the recycled water absorbent resin production step, the reusable water absorbent resin itself is treated as the recycled water absorbent resin. Examples of the recycled water absorbent resin production step include the following methods (A) and (B).

[0093] (A) A method for producing the "recycled water absorbent resin" by mixing a water absorbent resin produced by a normal method described below with the "reusable water absorbent resin".

[0094] (B) A method in which the "reusable water absorbent resin" is provided as a part of raw materials in at least one of the steps constituting a normal method for producing a water absorbent resin.

[0095] When the method (A) is adopted as the recycled water absorbent resin production process, the method of mixing the water absorbent resin produced by a normal method with the "reusable water absorbent resin" is not particularly limited, and a known mixing method can be applied. The mixing ratio of the water absorbent resin produced by a normal method with the "reusable water absorbent resin" may be appropriately determined according to the characteristics such as the water absorption performance of the target recycled water absorbent resin.

[0096] In the case where the method (B) is adopted as the manufacturing process of the recycled water absorbent resin, each step constituting the manufacturing process of the normal water absorbent resin is any one of a step of preparing an aqueous monomer solution, a polymerization step, a hydrous gel crushing step, a drying step, and a surface crosslinking step, which will be described later.

[0097] Each step constituting the normal production method for water absorbent resin will be described below. The production method for recycled water absorbent resin of the present invention may include each step constituting the normal production method for water absorbent resin described later.

[0098] <Preparation of Monomer Aqueous Solution> This step is a step of preparing an aqueous solution containing acrylic acid (salt) as a main component (hereinafter referred to as "aqueous monomer solution"). Although a slurry liquid of a monomer can be used within a range in which the water absorption performance of the obtained water absorbent resin is not deteriorated, for the sake of convenience, the aqueous monomer solution will be described in this section.

[0099] The "main component" means that the amount (content) of acrylic acid (salt) used is usually 50 mol % or more, preferably 70 mol % or more, and more preferably 90 mol % or more (upper limit: 100 mol %) based on the total amount of monomers (excluding internal crosslinking agents) used in the polymerization reaction of the water absorbent resin.

[0100] (acrylic acid) In one embodiment of the present invention, from the viewpoint of the physical properties and productivity of the obtained water absorbent resin, acrylic acid and / or a salt thereof (hereinafter referred to as "acrylic acid (salt)") is used as a monomer constituting the water absorbent resin.

[0101] The "acrylic acid" may be a known acrylic acid, and may contain a polymerization inhibitor in an amount of preferably 200 ppm or less, more preferably 10 ppm or more and 160 ppm or less, and even more preferably 20 ppm or more and 100 ppm or less, from the viewpoint of the polymerizability of the acrylic acid and the color tone of the water-absorbing resin. The polymerization inhibitor is preferably a methoxyphenol, more preferably p-methoxyphenol. As for impurities in acrylic acid, the compounds described in U.S. Patent Application Publication No. 2008 / 0161512 are also applicable to one embodiment of the present invention.

[0102] The "acrylate" is obtained by neutralizing the acrylic acid with the following basic composition. The acrylate may be a commercially available acrylate (e.g., sodium acrylate) or may be one obtained by neutralization in a water-absorbent resin manufacturing plant.

[0103] (Basic Composition) In one embodiment of the present invention, the term "basic composition" refers to a composition containing a basic compound, such as a commercially available aqueous sodium hydroxide solution.

[0104] Specific examples of the basic compound include carbonates and / or hydrogen carbonates of alkali metals, hydroxides of alkali metals, ammonia, organic amines, etc. Among these, from the viewpoint of the physical properties of the obtained water absorbent resin, it is desirable that the basic compound is strongly basic. That is, hydroxides of alkali metals such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferred, and sodium hydroxide is more preferred.

[0105] (neutralization) As the neutralization in one embodiment of the present invention, either neutralization of acrylic acid (before polymerization) or neutralization of a hydrogel-like crosslinked polymer obtained by crosslinking and polymerizing acrylic acid (after polymerization) (hereinafter referred to as "post-neutralization") can be selected or used in combination. In addition, these neutralizations may be either continuous or batchwise, and are not particularly limited, but continuous neutralization is preferred from the viewpoint of production efficiency, etc.

[0106] When the reusable water absorbent resin is used as a part of the raw material for the production of a water absorbent resin, the reusable water absorbent resin may contain a basic compound, which neutralizes the acrylic acid before polymerization or the hydrogel-like crosslinked polymer after polymerization. Therefore, as described later, the neutralization rate of the acrylic acid and the neutralization rate of the recycled water absorbent resin as the final product are adjusted to a predetermined range by taking into account the basic compound.

[0107] Regarding the conditions such as the neutralization apparatus, neutralization temperature, and residence time, the conditions described in International Publication No. 2009 / 123197 and US Patent Application Publication No. 2008 / 0194863 are also applied to the present invention.

[0108] In one embodiment of the present invention, the neutralization rate is preferably 10 mol% to 90 mol%, more preferably 40 mol% to 85 mol%, even more preferably 50 mol% to 80 mol%, and particularly preferably 60 mol% to 75 mol% based on the acid group of the monomer. If the neutralization rate is less than 10 mol%, the water absorption capacity may be significantly reduced. On the other hand, if the neutralization rate exceeds 90 mol%, a water absorbent resin with a high water absorption capacity under pressure may not be obtained. For example, a neutralization rate of 75 mol% means a mixture of 25 mol% acrylic acid and 75 mol% acrylic acid salt. The mixture may also be called a partially neutralized product of acrylic acid.

[0109] The neutralization rate is the same in the case of post-neutralization. The neutralization rate of the recycled water absorbent resin as a final product is also applied to the neutralization rate of the recycled water absorbent resin as a final product. When the reusable water absorbent resin contains the basic compound, the neutralization of the acrylic acid (before polymerization) and / or the post-neutralization of the hydrogel crosslinked polymer are appropriately adjusted so that the neutralization rate of the recycled water absorbent resin as a final product, including the basic compound, falls within a predetermined range.

[0110] (Other monomers) In one embodiment of the present invention, the term "other monomer" refers to a monomer other than the acrylic acid (salt), and the water-absorbing resin can be produced by using the other monomer together with the acrylic acid (salt).

[0111] The other monomer may be a water-soluble or hydrophobic unsaturated monomer. Specifically, the compounds described in U.S. Patent Application Publication No. 2005 / 0215734 (excluding acrylic acid) are also applicable to one embodiment of the present invention.

[0112] (Internal crosslinking agent) As the internal crosslinking agent used in one embodiment of the present invention, the compounds described in U.S. Patent No. 6,241,928 are also applied to one embodiment of the present invention. Among these, one or more compounds are selected in consideration of reactivity.

[0113] From the viewpoint of the water absorption performance of the obtained recycled water absorbent resin, a compound having two or more polymerizable unsaturated groups is preferably used as the internal crosslinking agent. More preferably, a compound having thermal decomposition properties at the drying temperature described below, and even more preferably a compound having two or more polymerizable unsaturated groups and a (poly)alkylene glycol structural unit, is used as the internal crosslinking agent.

[0114] The polymerizable unsaturated group is preferably an allyl group or a (meth)acrylate group, more preferably a (meth)acrylate group. The (poly)alkylene glycol structural unit is preferably polyethylene glycol, and the number n is preferably 1 or more and 100 or less, more preferably 6 or more and 50 or less.

[0115] The amount of the internal crosslinking agent used is preferably 0.0001% to 10 mol%, more preferably 0.001% to 1 mol%, based on the total monomer. By setting the amount used within the above range, a desired water-absorbing resin can be obtained. If the amount used is too small, the gel strength tends to decrease and the water-soluble components tend to increase, and if the amount used is too large, the water absorption capacity tends to decrease, which is not preferable. The mole % based on the total monomer refers to the percentage of the number of moles of the internal crosslinking agent relative to the total number of moles of the monomer contained in the aqueous monomer solution.

[0116] In one embodiment of the present invention, a method is preferably applied in which a predetermined amount of an internal crosslinking agent is added to an aqueous monomer solution in advance, and a crosslinking reaction is carried out simultaneously with polymerization. On the other hand, in addition to the above-mentioned method, a method of post-crosslinking by adding an internal crosslinking agent during and / or after polymerization, a radical crosslinking method using a radical polymerization initiator, a radiation crosslinking method using active energy rays such as electron beams and ultraviolet rays, etc. can also be adopted. These methods can also be used in combination.

[0117] (Other substances added to the monomer aqueous solution) In one embodiment of the present invention, from the viewpoint of improving the physical properties of the resulting water-absorbent resin, the following substances may be added during preparation of the aqueous monomer solution.

[0118] Specifically, hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (salts), and crosslinked polyacrylic acid (salts) can be added in amounts of preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (the lower limit is 0% by mass); foaming agents such as carbonates and azo compounds, surfactants, chelating agents, chain transfer agents, etc. can be added in amounts of preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (the lower limit is 0% by mass); and the like.

[0119] The substance may be added not only to the aqueous monomer solution but also during the polymerization, or these forms may be used in combination.

[0120] When a water-soluble resin or a water-absorbent resin is used as the hydrophilic polymer, a graft polymer or a water-absorbent resin composition (e.g., a starch-acrylic acid polymer, a PVA-acrylic acid polymer, etc.) is obtained. These polymers and water-absorbent resin compositions are also within the scope of the present invention.

[0121] <Polymerization process> This step is a step of polymerizing the acrylic acid (salt)-based monomer aqueous solution obtained in the step of preparing the monomer aqueous solution to obtain a hydrous gel crosslinked polymer (hereinafter referred to as "hydrous gel").

[0122] (Polymerization initiator) The polymerization initiator used in one embodiment of the present invention is not particularly limited since it is appropriately selected depending on the polymerization form, etc. For example, a thermally decomposable polymerization initiator, a photodecomposable polymerization initiator, or a redox-based polymerization initiator in combination with a reducing agent that promotes the decomposition of these polymerization initiators can be mentioned. Specifically, one or more of the polymerization initiators disclosed in U.S. Pat. No. 7,265,190 are used. From the viewpoint of the handling of the polymerization initiator, the physical properties of the water-absorbing resin, etc., preferably a peroxide or an azo compound is used, more preferably a peroxide, and even more preferably a persulfate.

[0123] The amount of the polymerization initiator used is preferably 0.001 mol% to 1 mol%, more preferably 0.001 mol% to 0.5 mol% based on the monomer. The amount of the reducing agent used is preferably 0.0001 mol% to 0.02 mol% based on the monomer. The mol% based on the monomer refers to the percentage of the number of moles of the reducing agent based on the total number of moles of the monomer contained in the aqueous monomer solution.

[0124] Instead of the polymerization initiator, the polymerization reaction may be carried out by irradiation with active energy rays such as radiation, electron beams, and ultraviolet rays, or these active energy rays may be used in combination with the polymerization initiator.

[0125] (polymerization form) The polymerization form applied to one embodiment of the present invention is not particularly limited, but from the viewpoint of water absorption characteristics, ease of polymerization control, etc., preferably, spray droplet polymerization, aqueous solution polymerization, and reversed phase suspension polymerization, more preferably, aqueous solution polymerization, and reversed phase suspension polymerization, and further preferably, aqueous solution polymerization are mentioned. Among them, continuous aqueous solution polymerization is particularly preferable, and either continuous belt polymerization or continuous kneader polymerization is applicable.

[0126] As specific polymerization forms, continuous belt polymerization is disclosed in U.S. Patent Nos. 4,893,999, 6,241,928, U.S. Patent Application Publication No. 2005 / 215734, etc., and continuous kneader polymerization is disclosed in U.S. Patent Nos. 6,987,151, 6,710,141, etc. By adopting these continuous aqueous solution polymerizations, the production efficiency of the water absorbent resin is improved.

[0127] In addition, preferred forms of the continuous aqueous solution polymerization include "high-temperature initiated polymerization" and "high-concentration polymerization." "High-temperature initiated polymerization" refers to a form in which polymerization is initiated at a temperature of the aqueous monomer solution of preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (upper limit is the boiling point). "High-concentration polymerization" refers to a form in which polymerization is performed at a monomer concentration of preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (upper limit is the saturated concentration). These polymerization forms can also be used in combination.

[0128] In one embodiment of the present invention, the polymerization can be carried out under an air atmosphere, but from the viewpoint of the color tone of the obtained water absorbent resin, it is preferable to carry out the polymerization under an inert gas atmosphere such as nitrogen or argon. In this case, for example, it is preferable to control the oxygen concentration to 1 volume % or less. It is also preferable to replace the dissolved oxygen in the aqueous monomer solution with an inert gas (for example, dissolved oxygen; less than 1 mg / l).

[0129] In one embodiment of the present invention, the polymerization may be carried out as foaming polymerization in which bubbles (particularly the inert gases or the like) are dispersed in an aqueous monomer solution to carry out the polymerization.

[0130] <Hydrous gel crushing process> In this step, the hydrogel obtained in the polymerization step is gel-pulverized by a screw extruder such as a kneader or a meat chopper, or a gel pulverizer such as a cutter mill, to obtain a particulate hydrogel (hereinafter referred to as a "particulate hydrogel"). When the polymerization step is kneader polymerization, the polymerization step and the gel pulverization step are carried out simultaneously. When the particulate hydrogel is obtained directly in the polymerization process, such as in gas phase polymerization or reversed phase suspension polymerization, the gel pulverization step may not be carried out.

[0131] As for the gel crushing conditions and forms other than those described above, the contents disclosed in WO 2011 / 126079 are preferably applied to the present invention.

[0132] <Particulate hydrous gel drying process> This step is a step of obtaining a dried polymer by drying the particulate hydrogel obtained in the polymerization step and / or hydrogel crushing step to a desired resin solid content. The drying method and suitable drying conditions in the particulate hydrogel drying step can be the same as those in the drying step described in the above section [2-8. Drying step, crushing and classification step].

[0133] By setting the above-mentioned drying temperature, drying time, etc. within the above-mentioned ranges, the CRC (absorbency), Ext (amount of water-soluble component) and color tone of the obtained recycled water absorbent resin can be set within the desired range.

[0134] <Surface crosslinking process> This step is a step of providing a part with a higher crosslink density on the surface layer (a part several tens of μm from the surface of the water-absorbent resin precursor) of the water-absorbent resin precursor obtained through the above-mentioned steps. The operation method and reaction conditions in the surface crosslinking step can be the operation method and reaction conditions described in the above [2-6. Surface crosslinking treatment step].

[0135] In the surface cross-linking step, a surface-cross-linked water-absorbent resin is obtained by radical cross-linking, surface polymerization, a cross-linking reaction with a surface cross-linking agent, or the like on the surface of the water-absorbent resin precursor.

[0136] [2-16. Modifications] As a modified example of the manufacturing method of the recycled water absorbent resin of the present invention, there can be mentioned a method in which the recovered water absorbent resin is supplied together with the water absorbent resin precursor to an apparatus for performing surface cross-linking in the surface cross-linking step in the manufacturing method of the normal water absorbent resin. The modified example is a method including each step of constituting the normal water absorbent resin described above in addition to the surface cross-linking treatment step, and optionally including each step for preparing the recovered water absorbent resin described above. The steps for preparing the recovered water absorbent resin are the absorbent article crushing (cutting) step, separation step, washing step, dehydration treatment step, drying step, and pulverization / classification step described above. In the modified example, the surface cross-linking step is performed on the water absorbent resin precursor to produce the normal water absorbent resin, and the surface cross-linking treatment step is performed on the recovered water absorbent resin to prepare a reusable water absorbent resin. As a result, according to the modified example, a recycled water absorbent resin is produced by mixing the normal water absorbent resin and the reusable water absorbent resin.

[0137] The present invention may also include the following inventions [1] to [5]. [1] A surface cross-linking treatment step of forming a cross-linked layer on a surface of a recovered water-absorbent resin recovered from a used absorbent article by using a surface cross-linking agent to obtain a reusable water-absorbent resin, The recovered water absorbent resin has a 5-minute water soluble component amount of 5% by mass or less and a 16-hour water soluble component amount of 10% by mass or more relative to the total mass of the recovered water absorbent resin. [2] The method for producing a recycled water absorbent resin according to [1], further comprising, before the surface cross-linking treatment step, carrying out a washing step of washing the water absorbent resin separated from a used absorbent article with washing water, and / or a dehydration treatment step of discharging the absorbed liquid. [3] The method for producing a recycled water absorbent resin according to [2], wherein the dehydration treatment step includes contacting the water absorbent resin separated from the used absorbent article with one or more selected from the group consisting of a polyvalent metal salt, an aqueous solution containing a polyvalent metal salt, an acidic liquid, a hydrophilic organic solvent, and an aqueous solution containing a hydrophilic organic solvent. [4] The method for producing a recycled water absorbent resin according to any one of [1] to [3], wherein the recovery rate of the CRC, represented by the following formula (1), is 80% or more. {CRC [g / g] of the reusable water-absorbent resin / CRC [g / g] of the water-absorbent resin contained in the absorbent article before use} × 100 (1) [5] The method for producing a recycled water absorbent resin according to any one of [1] to [4], wherein the recovery rate of AUL0.3, represented by the following formula (2), is 80% or more. {AUL0.3[g / g] of the reusable water-absorbent resin / AUL0.3[g / g] of the water-absorbent resin contained in the absorbent article before use}×100 (2) [6] The method for producing a recycled water absorbent resin according to any one of [1] to [5], wherein the recycled water absorbent resin has a recycling rate of 80% or more, which is represented by the following formula (3):

[0138] Recycling rate (%) = 100 - (amount of 16-hour water-soluble component of water-absorbent resin before recovery operation - amount of 16-hour water-soluble component of recovered water-absorbent resin) (3) The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. EXAMPLES

[0139] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the present invention is not limited to these examples. Examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention.

[0140] (Evaluation method) The physical properties of the recovered water absorbent resins obtained in Production Examples 1 to 10 and the reusable water absorbent resins (recycled water absorbent resins) obtained in Examples 1 to 5 and Comparative Examples 1 to 6 were measured and evaluated by the methods shown below.

[0141] (a) 5-minute water-soluble component amount, 16-hour water-soluble component amount The 5-minute water-soluble component amount and the 16-hour water-soluble component amount of the recovered water-absorbent resin were measured according to the following procedure.

[0142] <Adjusting the particle size of water-absorbent resin> The recovered water-absorbent resin was sieved through 300 μm and 600 μm sieves, and the resin that passed through the 600 μm sieve and remained on the 300 μm sieve was collected.

[0143] <Measurement of solid content> A water-absorbent resin (solution) having a mass Wa (g) was placed on an aluminum plate having a mass Wb (g) and dried in a hot air circulating oven at 180°C for 3 hours. Thereafter, the total mass Wc (g) of the dried water-absorbent resin (solution) and the aluminum plate was measured. The solid content concentration of the water-absorbent resin (solution) was calculated according to the following formula (4).

[0144] Solids concentration (mass%) of water-absorbent resin (solution) = (Wc - Wb) / Wa × 100 (4) <Sample collection> 100 g of physiological saline was weighed into each of two 120 ml beakers, a 20 mm stirrer tip was added, and stirring was performed with a magnetic stirrer (500 rpm). The particle size-adjusted water-absorbent resin was precisely weighed to obtain two 0.50 g pieces of water-absorbent resin. One of the obtained 0.50 g pieces of water-absorbent resin was poured into the stirred physiological saline in one of the beakers at once. Five minutes after the pouring, about 2 mL of the solution present in the one of the beakers was collected with a syringe and passed through a filter (GL Sciences: GL Chromatodisc, water-based 25A, pore size 0.2 μm) to prepare measurement sample A. Similarly, the other of the obtained 0.50 g pieces of water-absorbent resin was poured into the stirred physiological saline in the other 120 ml beaker at once. 16 hours after the pouring, about 2 mL of the solution present in the other beaker was collected with a syringe, and measurement sample B was prepared in the same manner as in the preparation of measurement sample A. GPC measurements were performed under the following measurement conditions for each of the measurement sample A and the measurement sample B. In the following, the physiological saline solution into which 0.50 g of the water-absorbent resin was added is referred to as a "water-absorbent resin solution."

[0145] <GPC Measurement> Using a Viscotek TDAmax manufactured by Malvern Instruments, GPC measurements were performed on each of measurement sample A and measurement sample B. The measuring device was equipped with size exclusion chromatography, a refractive index detector, a light scattering detector, and a capillary viscometer. The measuring device and measurement conditions were as follows. Pump, autosampler: Viscotek GPCmax (manufactured by Malvern Instruments) Guard column: OHpak SB-G (manufactured by Showa Denko K.K.) Column: Two OHpak SB-806MHQ (manufactured by Showa Denko K.K.) were connected in series and used. Detector: Viscotek TDAmax (manufactured by Malvern Instruments) Solvent: An aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM disodium hydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH in the range of 6.35 or more and 6.38 or less) Flow rate: 0.5 ml / min Injection volume: 100 μl As the water used in the GPC measurement, pure water with sufficiently removed impurities was used. Also, the GPC measurement was performed in a state where the baseline of the detector was stable, particularly in a state where there was no noise peak in the refractive index detector.

[0146] <Calibration Curve Preparation> Using a 30 mass% aqueous solution of polyacrylic acid (manufactured by Nippon Shokubai Co., Ltd.; unneutralized product of Aquaric DL-522, mass average molecular weight (Mw) 390,000 g / mol), several solutions with different polyacrylic acid concentrations were prepared, and GPC measurements were performed under the above-described measurement conditions. From the refractive index (RI) data, a calibration curve of polyacrylic acid concentration - RI area value was prepared.

[0147] <Quantification of Water-Soluble Component Amount> GPC measurements were performed on each of measurement sample A and measurement sample B, and the RI area value was measured. Based on the measured RI area value and the calibration curve prepared by the method described in the <Calibration Curve Preparation> column, the concentration of polyacrylic acid contained in the measurement sample was calculated.

[0148] Furthermore, the "amount of water-soluble component" was calculated using the following formula (5). The amount of water-soluble component calculated from the following formula (5) using the RI area value measured for measurement sample A is the "amount of water-soluble component for 5 minutes." The amount of water-soluble component calculated from the following formula (5) using the RI area value measured for measurement sample B is the "amount of water-soluble component for 16 hours." The "amount of water-soluble component for 5 minutes" is also referred to as the "5-minute value" of the amount of water-soluble component, and the "amount of water-soluble component for 16 hours" is also referred to as the "16-hour value" of the amount of water-soluble component.

[0149] Amount of water-soluble component (mass%) = (concentration of polyacrylic acid in the measurement sample) / (concentration of water-absorbent resin in the water-absorbent resin solution) × 100 (5) (c)CRC The CRC of the water-absorbent resin was measured by the method described below.

[0150] 0.200 g of water-absorbent resin was evenly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Industrial Co., Ltd., product name: Heatlon Paper, model: GSP-22), heat-sealed, and then immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag was pulled out and drained for 3 minutes using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122) at a centrifugal force (250 G) described in EDANA ABSORBENCY II 441.1-99, and the mass W1 (g) of the bag was measured. In addition, the same operation was performed without using the water-absorbent resin, and the mass W0 (g) at that time was measured. Then, from these W1 and W0, the CRC (centrifuge retention capacity) was calculated according to the following formula (6). CRC(g / g)={(W1-W0) / (mass of water-absorbent resin)}-1 (6) (d) AUL0.3 The AUL0.3 of the water-absorbent resin was measured by the method described below.

[0151] A stainless steel 400 mesh wire net was fused to the bottom of a plastic support cylinder with an inner diameter of 25 mm. Next, 0.16 g of water-absorbent resin was evenly spread on the net under the conditions of room temperature (within the range of 20°C to 25°C) and humidity of 50 RH%. On top of the net, a piston with an outer diameter slightly smaller than 25 mm, which was adjusted so that a load of 2.07 kPa (0.3 psi) could be evenly applied to the water-absorbent resin, which did not create a gap with the support cylinder, and which did not hinder the up and down movement, and a load were placed in that order. Next, the mass W2 (g) of the entire measuring device was measured.

[0152] A 90 mm diameter glass filter (manufactured by Sogo Rikagaku Glass Works, pore diameter: 100 μm to 120 μm) was placed inside a 150 mm diameter Petri dish, and a 0.90 mass % sodium chloride aqueous solution (temperature: 20 ° C. to 25 ° C.) was added to the same level as the upper surface of the glass filter. A 90 mm diameter filter paper (ADVANTEC Toyo Co., Ltd., product name: (JIS P 3801, No. 2), thickness 0.26 mm, retention particle size 5 μm) was placed on top of it, so that the entire surface was wet and excess liquid was removed. The measuring device set was placed on the filter paper and the liquid was absorbed under load. After 1 hour, the measuring device set was lifted and its mass W3 (g) was measured. Then, AUL0.3 was calculated from W2 and W3 according to the following formula (7). AUL0.3(g / g)=(W3-W2) / (mass of water-absorbent resin)(7) (e) Recycling rate The recycling rate of the recovered water absorbent resin was calculated according to the following formula (3).

[0153] Recycling rate (%) = 100 - (amount of 16-hour water-soluble component of water-absorbent resin before recovery operation - amount of 16-hour water-soluble component of recovered water-absorbent resin) (3) In this embodiment, the "amount of 16-hour water-soluble component of the water absorbent resin before the recovery operation" is specifically the "amount of 16-hour water-soluble component of the simulated used water absorbent resin before the recovery operation, i.e., the washing step and the dehydration step, is performed".

[0154] [Production Example 1: Production of water-absorbent resin (1)] 100 parts by mass of acrylic acid, 159 parts by mass of ion-exchanged water, and 0.33 parts by mass of polyethylene glycol diacrylate (molecular weight 523) were added to a reaction vessel and stirred. Next, the reaction vessel was immersed in an ice bath, and 81.3 parts by mass of an aqueous sodium hydroxide solution (solid content concentration 48.5% by mass) was added little by little while stirring so that the temperature of the reaction liquid did not exceed 30°C, and then the reaction liquid was purged with nitrogen gas for 30 minutes.

[0155] Next, the reaction solution was immersed in a 50°C warm water bath while stirring, and when the temperature of the reaction solution reached 30°C, 0.182 parts of sodium persulfate and 0.0007g of L-ascorbic acid were added, and polymerization started about 10 minutes later. Thereafter, polymerization was carried out while immersed in the warm water bath, and 60 minutes after the start of polymerization, the hydrogel-like crosslinked polymer (1) was taken out. The obtained hydrogel-like crosslinked polymer (1) was gel-crushed with a meat chopper having a die diameter of 7.5 mm, and then dried with hot air at 190°C for 60 minutes. Next, the dried product was crushed using a vibration mill, and further classified with JIS standard sieves with openings of 850 μm and 150 μm, to obtain an irregularly crushed water-absorbent resin precursor (1).

[0156] A surface crosslinking agent solution consisting of 0.040 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water was uniformly mixed with 100 parts by mass of the obtained water absorbent resin precursor (1), and heat-treated at 100°C for 45 minutes. The mixture was then cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a water absorbent resin (1). The obtained water absorbent resin (1) had an average particle size of 360 μm, a CRC of 41.4 g / g, and an AUL0.3 of 31.6 g / g.

[0157] [Production Example 2: Production of simulated used water absorbent resin (1)] 1700 parts by mass of 0.9% by mass sodium chloride aqueous solution (physiological saline) was added to 50 parts by mass of the water absorbent resin (1) obtained in Production Example 1, and the mixture was left at 37°C for 72 hours or more and mixed thoroughly to obtain a simulated used water absorbent resin (1). The amount of water-soluble components in this simulated used water absorbent resin (1) was 34.4% by mass after 16 hours.

[0158] [Production Example 3: Preparation of Recovered Water Absorbent Resin (1)] 140 g of the simulated used water absorbent resin (1) obtained in Production Example 2 (water absorbent resin solid content: 4.0 g) and 256 g of physiological saline were added to a beaker, and the mixture was stirred for 15 minutes to perform a cleaning treatment. The contents of the beaker were then filtered through a 100-mesh stainless steel wire net, and 237 g of the filtrate was returned to the beaker. 237 g of acetone was added thereto, and the mixture was stirred for 15 minutes to perform a dehydration treatment. The contents of the beaker were then filtered through a 100-mesh stainless steel wire net, and the filtrate was dried in an oven at 180°C for 2 hours.

[0159] The dried product was then pulverized using a vibration mill to obtain a pulverized product. The pulverized product was then classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain a recovered water absorbent resin (1) in an irregularly pulverized state. The recovered water absorbent resin (1) thus obtained had an average particle size of 410 μm, a CRC of 48.0 g / g, and an AUL0.3 of 8.4 g / g. The amount of water-soluble components in the recovered water absorbent resin (1) was 2.9% by mass after 5 minutes and 21.5% by mass after 16 hours.

[0160] [Production Example 4: Preparation of Recovered Water Absorbent Resin (2)] A cleaning treatment was carried out in the same manner as in Production Example 3, except that the amount of physiological saline used was changed to 656 g. The obtained beaker contents were then filtered through a 100-mesh stainless steel wire screen, and 240 g of the filtrate was returned to the beaker, and dehydration, drying, pulverization, and classification were carried out in the same manner as in Production Example 3, except that 240 g of acetone was added thereto. As a result, an irregularly crushed recovered water absorbent resin (2) was obtained. The obtained recovered water absorbent resin (2) had an average particle size of 420 μm, a CRC of 47.9 g / g, and an AUL0.3 of 9.2 g / g. The amount of water-soluble components in this recovered water absorbent resin (2) was 1.1% by mass in 5 minutes and 15.2% by mass in 16 hours.

[0161] [Production Example 5: Preparation of Recovered Water Absorbent Resin (3)] A washing treatment was carried out in the same manner as in Production Example 3, except that 256 g of deionized water was used instead of physiological saline. The obtained beaker contents were then filtered through a 100-mesh stainless steel wire screen, and 337 g of the filtrate was returned to the beaker, and dehydration, drying, pulverization, and classification were carried out in the same manner as in Production Example 3, except that 337 g of acetone was added thereto. As a result, an irregularly crushed recovered water absorbent resin (3) was obtained. The obtained recovered water absorbent resin (3) had an average particle size of 410 μm, a CRC of 50.8 g / g, and an AUL0.3 of 8.9 g / g. The amount of water-soluble components in this recovered water absorbent resin (3) was 1.3% by mass in 5 minutes and 15.0% by mass in 16 hours.

[0162] [Production Example 6: Preparation of Recovered Water Absorbent Resin (4)] Into a beaker, 140 g of the simulated used water absorbent resin (1) obtained in Production Example 2 (water absorbent resin solid content 4.0 g) and 200 g of a 1.7 mass% calcium chloride aqueous solution were added, and the mixture was stirred for 15 minutes to perform a dehydration treatment. Subsequently, the contents of the beaker after the dehydration treatment were filtered through a 100-mesh stainless steel wire mesh, and 12.4 g of the filtrate was returned to the beaker. Thereto, 22.9 g of 2M hydrochloric acid and 177.1 g of deionized water were added, and the mixture was stirred for 15 minutes to perform an acid treatment. Subsequently, the contents of the beaker after the acid treatment were filtered through a 100-mesh stainless steel wire mesh, and 40.8 g of the filtrate was returned to the beaker again. Thereto, 300 g of deionized water was added, and the mixture was stirred for 15 minutes to perform a cleaning treatment. Subsequently, the contents of the beaker after the cleaning treatment were filtered through a 100-mesh stainless steel wire mesh, and 45.6 g of the filtrate was returned to the beaker. While stirring the filtered product with a spatula, 2.85 g of a 45% by mass aqueous solution of sodium hydroxide was added dropwise, and stirring was continued for 2 minutes, after which the product was left to stand for 20 minutes and then dried in an oven at 180° C. for 2 hours.

[0163] Next, the dried product was pulverized and classified in the same manner as in Production Example 3. As a result, an irregularly pulverized recovered water absorbent resin (4) was obtained. The recovered water absorbent resin (4) had an average particle size of 400 μm, a CRC of 49.8 g / g, and an AUL0.3 of 8.5 g / g. The amount of water-soluble components in the recovered water absorbent resin (4) was 1.2% by mass after 5 minutes and 17.4% by mass after 16 hours.

[0164] [Production Example 7: Preparation of Recovered Water Absorbent Resin (5)] In a beaker, 140 g of the simulated used water absorbent resin (1) obtained in Production Example 2 (water absorbent resin solid content 4.0 g) and 440 g of a 3.0 mass% citric acid aqueous solution were added, and the mixture was stirred for 15 minutes to perform a dehydration treatment (also serving as an acid treatment). The contents of the beaker were then filtered through a 100-mesh stainless steel wire net, and 62.4 g of the filtrate was returned to the beaker. 320 g of deionized water was added thereto, and the mixture was stirred for 15 minutes to perform a cleaning treatment. The contents of the beaker were then filtered through a 100-mesh stainless steel wire net, and 97.6 g of the filtrate was returned to the beaker. While stirring the filtrate with a spatula, 2.85 g of a 45 mass% sodium hydroxide aqueous solution was dropped, and stirring was continued for 2 minutes. The mixture was then left for 20 minutes, and then dried in an oven at 180 ° C. for 3 hours.

[0165] Next, the dried product was pulverized and classified in the same manner as in Production Example 3. As a result, an irregularly pulverized recovered water absorbent resin (5) was obtained. The recovered water absorbent resin (5) had an average particle size of 420 μm, a CRC of 45.9 g / g, and an AUL0.3 of 9.6 g / g. The amount of water-soluble components in the recovered water absorbent resin (5) was 1.2% by mass after 5 minutes and 13.7% by mass after 16 hours.

[0166] [Production Example 8: Preparation of Comparative Recovered Water Absorbent Resin (1)] In a beaker, 140 g of the simulated used water absorbent resin (1) obtained in Production Example 2 (water absorbent resin solid content: 4.0 g) and 140 g of acetone were added, and the mixture was stirred for 15 minutes to carry out a dehydration treatment. Subsequently, the content of the beaker was filtered through a 100-mesh stainless steel wire screen, and the filtered product was dried in an oven at 180°C for 2 hours without washing.

[0167] Next, the dried product was pulverized and classified in the same manner as in Production Example 3. As a result, a comparative recovered water absorbent resin (1) in an irregularly pulverized form was obtained. The comparative recovered water absorbent resin (1) thus obtained had an average particle size of 400 μm, a CRC of 42.2 g / g, and an AUL0.3 of 7.4 g / g. The water-soluble component content of this comparative recovered water absorbent resin (1) was 8.1% by mass after 5 minutes and 24.6% by mass after 16 hours.

[0168] [Production Example 9: Preparation of Comparative Recovered Water Absorbent Resin (2)] In a beaker, 140 g of the simulated used water absorbent resin (1) obtained in Production Example 2 (water absorbent resin solid content 4.0 g) and 123 g of physiological saline were added, and the mixture was stirred for 15 minutes to perform a washing treatment. Then, the contents of the beaker were filtered through a 100-mesh stainless steel wire net, and 224 g of the filtrate was returned to the beaker. 224 g of acetone was added thereto, and the mixture was stirred for 15 minutes to perform a dehydration treatment. Then, the contents of the beaker were filtered through a 100-mesh stainless steel wire net, and the filtrate was dried in an oven at 180°C for 2 hours.

[0169] Next, the dried product was pulverized and classified in the same manner as in Production Example 3. As a result, a comparative recovered water absorbent resin (2) in an irregularly pulverized form was obtained. The comparative recovered water absorbent resin (2) thus obtained had an average particle size of 420 μm, a CRC of 46.7 g / g, and an AUL0.3 of 8.8 g / g. The water-soluble component content of this comparative recovered water absorbent resin (2) was 5.4% by mass after 5 minutes and 18.8% by mass after 16 hours.

[0170] [Production Example 10: Preparation of Comparative Recovered Water Absorbent Resin (3)] 140 g of the simulated used water absorbent resin (1) obtained in Production Example 2 (water absorbent resin solid content: 4.0 g) and 56 g of physiological saline were added to a beaker, and the mixture was stirred for 15 minutes to perform a cleaning treatment. Then, the contents of the beaker were filtered through a 100-mesh stainless steel wire net, and 200 g of the filtrate was returned to the beaker. 200 g of acetone was added thereto, and the mixture was stirred for 15 minutes to perform a dehydration treatment. Then, the contents of the beaker were filtered through a 100-mesh stainless steel wire net, and the filtrate was dried in an oven at 180°C for 2 hours.

[0171] Next, the dried product was pulverized and classified in the same manner as in Production Example 3. As a result, a comparative recovered water absorbent resin (3) in an irregularly pulverized form was obtained. The comparative recovered water absorbent resin (3) thus obtained had an average particle size of 430 μm, a CRC of 46.7 g / g, and an AUL0.3 of 8.5 g / g. The amount of water-soluble components in this comparative recovered water absorbent resin (3) was 8.0% by mass after 5 minutes and 24.7% by mass after 16 hours.

[0172] [Production Example 11: Production of Comparative Recovered Water Absorbent Resin (4)] Into a beaker, 140 g of the simulated used water absorbent resin (1) obtained in Production Example 2 (water absorbent resin solid content 4.0 g) and 656 g of physiological saline were added, and the mixture was stirred for 15 minutes to perform a cleaning treatment. Then, the contents of the beaker were filtered through a 100-mesh stainless steel wire mesh, and 240 g of the filtrate was returned to the beaker. 240 g of acetone was added thereto, and the mixture was stirred for 15 minutes to perform a dehydration treatment. Then, the contents of the beaker were filtered through a 100-mesh stainless steel wire mesh, and 19.1 g of the filtrate was returned to the beaker. 656 g of physiological saline was added thereto, and the mixture was stirred for 15 minutes to perform a cleaning treatment (second time). Then, the contents of the beaker were filtered through a 100-mesh stainless steel wire mesh, and 220 g of the filtrate was returned to the beaker. 220 g of acetone was added thereto, and the mixture was stirred for 15 minutes to perform a dehydration treatment (second time).

[0173] Next, the dried product was pulverized and classified in the same manner as in Production Example 3. As a result, a comparative recovered water absorbent resin (4) in an irregularly pulverized form was obtained. The comparative recovered water absorbent resin (4) thus obtained had an average particle size of 430 μm, a CRC of 46.5 g / g, and an AUL0.3 of 8.8 g / g. The amount of water-soluble components in this comparative recovered water absorbent resin (4) was 0.6% by mass after 5 minutes and 3.2% by mass after 16 hours.

[0174] [Result A: Evaluation of the physical properties of the recovered water-absorbent resin] The physical properties of the water absorbent resin (1) obtained in Production Example 1, and the recovered water absorbent resins (1) to (5) and comparative recovered water absorbent resins (1) to (4) obtained in Production Examples 3 to 11 are shown in the following Table 1. Note that the "CRC recovery rate" in the following Table 1 is the CRC recovery rate relative to the CRC of the water absorbent resin (1), and the "AUL0.3 recovery rate" is the AUL0.3 recovery rate relative to the AUL0.3 of the water absorbent resin (1).

[0175] [Table 1]

[0176] From the results in Table 1, it was found that the recovered water absorbent resins (1) to (5) prepared in Production Examples 3 to 11 and the comparative recovered water absorbent resins (1) to (4) all had a significantly decreased AUL0.3 compared to the water absorbent resin (1) in Production Example 1. This is considered to be due to the destruction of the surface cross-linked layer of the water absorbent resin by the swelling caused by the addition of physiological saline and the heat treatment shown in Production Example 2.

[0177] In addition, in the recovered water absorbent resins (1) to (5) and the comparative recovered water absorbent resin (4) prepared by washing and dehydrating in Production Examples 3 to 7 and 11, the 5-minute value of the amount of water-soluble component was 5% by mass or less. This is considered to be because the amount of water-soluble component attached to the surface of the water absorbent resin was small.

[0178] On the other hand, in Production Example 8, the comparative recovered water absorbent resin (1) prepared by only carrying out the dehydration treatment without carrying out the washing treatment has a very high 5-minute value of the water-soluble component amount of 8.1 mass %. In addition, the comparative recovered water absorbent resins (2) and (3) prepared in Production Examples 9 and 10 were subjected to the same washing treatment and dehydration treatment as in Production Example 3, but the 5-minute value of the water-soluble component amount was more than 5 mass %. This is considered to be because the water-soluble component attached to the surface of the water absorbent resin was not sufficiently washed away due to the high concentration of the water absorbent resin during the washing treatment.

[0179] In Production Example 11, the comparative recovered water absorbent resin (4) prepared by carrying out the washing treatment and the dehydration treatment twice each had a water-soluble component amount of less than 10 mass% after 16 hours. This is considered to be because a large amount of water-soluble components was removed from the entire simulated used water absorbent resin (1) by the washing treatment and the dehydration treatment.

[0180] [Example 1: Production of recycled water absorbent resin (1)] A surface crosslinking agent composition liquid (ethylene glycol diglycidyl ether / propylene glycol (PG) / water=0.05 parts by mass / 1.5 parts by mass / 3.5 parts by mass) was mixed with 100 parts by mass of the recovered water absorbent resin (1) obtained in Production Example 3, and the mixture was heated at 100° C. for 60 minutes to obtain a reusable water absorbent resin. The obtained reusable water absorbent resin was designated as a recycled water absorbent resin (1).

[0181] The recycled water absorbent resin (1) thus obtained had a CRC of 42.5 g / g and an AUL0.3 of 29.8 g / g. The CRC recovery rate of the recycled water absorbent resin (1) was 102.7% and the AUL0.3 recovery rate of the recycled water absorbent resin (1) was 94.3% relative to the water absorbent resin (1).

[0182] [Example 2: Production of recycled water absorbent resin (2)] A reusable water absorbent resin was obtained in the same manner as in Example 1, except that the recovered water absorbent resin (2) obtained in Production Example 4 was used instead of the recovered water absorbent resin (1). The obtained reusable water absorbent resin was designated as recycled water absorbent resin (2).

[0183] The obtained recycled water absorbent resin (2) had a CRC of 41.6 g / g and an AUL0.3 of 31.5 g / g. The CRC recovery rate of the recycled water absorbent resin (2) relative to the water absorbent resin (1) was 100.5%, and the AUL0.3 recovery rate was 99.7%.

[0184] [Example 3: Production of recycled water absorbent resin (3)] A reusable water absorbent resin was obtained in the same manner as in Example 1, except that the recovered water absorbent resin (3) obtained in Production Example 5 was used instead of the recovered water absorbent resin (1). The obtained reusable water absorbent resin was designated as a recycled water absorbent resin (3).

[0185] The obtained recycled water absorbent resin (3) had a CRC of 40.6 g / g and an AUL0.3 of 31.7 g / g. The CRC recovery rate of the recycled water absorbent resin (3) relative to the water absorbent resin (1) was 98.1%, and the AUL0.3 recovery rate was 100.3%.

[0186] [Example 4: Production of recycled water absorbent resin (4)] A reusable water absorbent resin was obtained in the same manner as in Example 1, except that the recovered water absorbent resin (4) obtained in Production Example 6 was used instead of the recovered water absorbent resin (1). The obtained reusable water absorbent resin was designated as a recycled water absorbent resin (4).

[0187] The obtained recycled water absorbent resin (4) had a CRC of 40.1 g / g and an AUL0.3 of 31.5 g / g. The CRC recovery rate of the recycled water absorbent resin (4) relative to the water absorbent resin (1) was 96.9%, and the AUL0.3 recovery rate was 99.7%.

[0188] [Example 5: Production of recycled water absorbent resin (5)] A reusable water absorbent resin was obtained in the same manner as in Example 1, except that the recovered water absorbent resin (5) obtained in Production Example 7 was used instead of the recovered water absorbent resin (1). The obtained reusable water absorbent resin was designated as a recycled water absorbent resin (5).

[0189] The obtained recycled water absorbent resin (5) had a CRC of 35.6 g / g and an AUL0.3 of 29.5 g / g. The CRC recovery rate of the recycled water absorbent resin (5) relative to the water absorbent resin (1) was 86.0%, and the AUL0.3 recovery rate was 93.4%.

[0190] [Comparative Example 1: Production of Comparative Recycled Water Absorbent Resin (1)] The recycled water absorbent resin precursor (3) obtained in Production Example 3 was not subjected to surface cross-linking treatment and was used as it was to prepare a comparative recycled water absorbent resin (1).

[0191] The comparative recycled water absorbent resin (1) thus obtained had a CRC of 47.9 g / g and an AUL0.3 of 8.2 g / g. The comparative recycled water absorbent resin (1) had a CRC recovery rate of 115.7% and an AUL0.3 recovery rate of 25.9% relative to the water absorbent resin (1).

[0192] [Comparative Example 2: Production of Comparative Recycled Water Absorbent Resin (2)] A comparative reusable water absorbent resin was obtained in the same manner as in Example 1, except that the comparative recovered water absorbent resin (1) obtained in Production Example 8 was used instead of the recovered water absorbent resin (1). The comparative reusable water absorbent resin obtained was designated as a comparative recycled water absorbent resin (2).

[0193] The comparative recycled water absorbent resin (2) thus obtained had a CRC of 38.2 g / g and an AUL0.3 of 10.5 g / g. The comparative recycled water absorbent resin (2) had a CRC recovery rate of 92.3% and an AUL0.3 recovery rate of 33.2% relative to the water absorbent resin (1).

[0194] [Comparative Example 3: Production of Comparative Recycled Water Absorbent Resin (3)] A comparative reusable water absorbent resin was obtained in the same manner as in Example 1, except that the comparative recovered water absorbent resin (1) obtained in Production Example 8 was used instead of the recovered water absorbent resin (1) and the composition of the surface crosslinking agent composition liquid was changed to ethylene glycol diglycidyl ether / propylene glycol (PG) / water = 0.10 parts by mass / 1.5 parts by mass / 3.5 parts by mass. The comparative reusable water absorbent resin obtained was designated as a comparative recycled water absorbent resin (3).

[0195] The comparative recycled water absorbent resin (3) thus obtained had a CRC of 34.2 g / g and an AUL0.3 of 15.1 g / g. The comparative recycled water absorbent resin (3) also had a CRC recovery rate of 82.6% and an AUL0.3 recovery rate of 47.8% relative to the water absorbent resin (1).

[0196] [Comparative Example 4: Production of Comparative Recycled Water Absorbent Resin (4)] A comparative reusable water absorbent resin was obtained in the same manner as in Example 1, except that the comparative recovered water absorbent resin (1) obtained in Production Example 8 was used instead of the recovered water absorbent resin (1) and the composition of the surface crosslinking agent composition liquid was changed to ethylene glycol diglycidyl ether / propylene glycol (PG) / water = 0.15 parts by mass / 1.5 parts by mass / 3.5 parts by mass. The comparative reusable water absorbent resin obtained was designated as a comparative recycled water absorbent resin (4).

[0197] The comparative recycled water absorbent resin (4) thus obtained had a CRC of 31.5 g / g and an AUL0.3 of 18.7 g / g. The comparative recycled water absorbent resin (4) also had a CRC recovery rate of 76.1% and an AUL0.3 recovery rate of 59.2% relative to the water absorbent resin (1).

[0198] [Comparative Example 5: Production of Comparative Recycled Water Absorbent Resin (5)] A comparative reusable water absorbent resin was obtained in the same manner as in Example 1, except that the comparative recovered water absorbent resin (2) obtained in Production Example 9 was used instead of the recovered water absorbent resin (1). The comparative reusable water absorbent resin obtained was designated as a comparative recycled water absorbent resin (5).

[0199] The comparative recycled water absorbent resin (5) thus obtained had a CRC of 42.9 g / g and an AUL0.3 of 17.3 g / g. The comparative recycled water absorbent resin (5) also had a CRC recovery rate of 103.6% and an AUL0.3 recovery rate of 54.7% relative to the water absorbent resin (1).

[0200] [Comparative Example 6: Production of Comparative Recycled Water Absorbent Resin (6)] A comparative reusable water absorbent resin was obtained in the same manner as in Example 1, except that the comparative recovered water absorbent resin (3) obtained in Production Example 10 was used instead of the recovered water absorbent resin (1). The comparative reusable water absorbent resin obtained was designated as a comparative recycled water absorbent resin (6).

[0201] The comparative recycled water absorbent resin (6) thus obtained had a CRC of 41.6 g / g and an AUL0.3 of 9.0 g / g. The comparative recycled water absorbent resin (6) also had a CRC recovery rate of 100.5% and an AUL0.3 recovery rate of 28.5% relative to the water absorbent resin (1).

[0202] [Comparative Example 7: Production of Comparative Recycled Water Absorbent Resin (7)] A comparative reusable water absorbent resin was obtained in the same manner as in Example 1, except that the comparative recovered water absorbent resin (4) obtained in Production Example 11 was used instead of the recovered water absorbent resin (1). The comparative reusable water absorbent resin obtained was designated as a comparative recycled water absorbent resin (7).

[0203] The comparative recycled water absorbent resin (7) thus obtained had a CRC of 39.2 g / g and an AUL0.3 of 32.6 g / g. The comparative recycled water absorbent resin (7) also had a CRC recovery rate of 94.7% and an AUL0.3 recovery rate of 103.2% relative to the water absorbent resin (1).

[0204] [Result B: Evaluation of the physical properties of recycled water absorbent resin] The physical properties of the recycled water absorbent resins (1) to (5) and the comparative recycled water absorbent resins (1) to (7) obtained in Examples 1 to 5 and Comparative Examples 1 to 7 are shown in Table 2 below. In addition, for reference, the CRC and AUL0.3 values ​​of the water absorbent resin (1) obtained in Production Example 1 are also shown in Table 2. The "recycle rate" described in Table 2 is the ratio of the mass of the obtained recycled water absorbent resins (1) to (5) and the comparative recycled water absorbent resins (1) to (7) to the mass of the simulated used water absorbent resin (1) that is the raw material. In addition, as in Table 1, the "CRC recovery rate" described in Table 2 is the CRC recovery rate relative to the CRC of the water absorbent resin (1), and the "AUL0.3 recovery rate" is the AUL0.3 recovery rate relative to the AUL0.3 of the water absorbent resin (1). Furthermore, the "crosslinking agent" described in Table 2 is "ethylene glycol diglycidyl ether".

[0205] [Table 2]

[0206] As shown in Table 2, the recycled water absorbent resins (1) to (5) described in Examples 1 to 5 have a large improvement in AUL0.3, and are excellent in both CRC and AUL0.3. The recycled water absorbent resins (1) to (5) were obtained by subjecting the recovered water absorbent resins (1) to (5) having a 5-minute water soluble content of 5% by mass or less to a surface crosslinking treatment. Furthermore, the comparative recycled water absorbent resin (1) described in Comparative Example 1, which was obtained by using the recovered water absorbent resin (1) as it is without subjecting it to a surface crosslinking treatment, has a low AUL0.3. From the above, it was found that in Examples 1 to 5, the recovered water absorbent resins (1) to (5) that were the subject of the surface crosslinking treatment had a 5-minute water soluble content of 5% by mass or less, and therefore the surface crosslinking proceeded well, and as a result, the AUL0.3 recovery rate was sufficiently high.

[0207] The comparative recycled water absorbent resin (2) described in Comparative Example 2 showed little improvement in AUL0.3, and the AUL0.3 recovery rate was insufficient compared to the water absorbent resin (1). The comparative recycled water absorbent resin (2) was obtained by subjecting the comparative recovered water absorbent resin (1) having a 5-minute water soluble component amount exceeding 5 mass% to a surface crosslinking treatment. From the above, it was found that in Comparative Example 2, the comparative recovered water absorbent resin (1) to be surface crosslinked had a 5-minute water soluble component amount exceeding 5 mass%, and therefore the surface crosslinking did not proceed well, resulting in an insufficient AUL0.3 recovery rate.

[0208] In Comparative Examples 3 and 4, the amount of crosslinking agent during surface treatment was increased compared to Comparative Example 2, aiming to improve the degree of surface crosslinking. As a result, AUL0.3 was increased. However, in the comparative recycled water absorbent resins (3) and (4) obtained in Comparative Examples 3 and 4, the AUL0.3 recovery rate relative to the water absorbent resin (1) was insufficient. This is thought to be due to the fact that the amount of 5-minute water-soluble components in the comparative recycled water absorbent resin (1), which is the subject of the surface crosslinking treatment, exceeds 5 mass%, and therefore the surface crosslinking does not proceed well even in Comparative Examples 3 and 4.

[0209] In addition, the CRC recovery rate of the comparative recycled water absorbent resins (3) and (4) is also lower than that of the water absorbent resin (1). Therefore, it was found that a recycled water absorbent resin having an excellent balance of physical properties between the water absorbency without pressure and the water absorbency under pressure cannot be obtained by increasing the amount of the crosslinking agent during the surface treatment.

[0210] The comparative recycled water absorbent resins (2) and (3) described in Comparative Examples 5 and 6 showed little improvement in AUL0.3 and insufficient AUL0.3 recovery rate. The comparative recycled water absorbent resins (2) and (3) were obtained by subjecting the comparative recovered water absorbent resins (2) and (3) having a 5-minute water soluble content exceeding 5% by mass to surface crosslinking treatment. From the above, it was found that the surface crosslinking did not proceed well in Comparative Examples 5 and 6 because the 5-minute water soluble content of the comparative recovered water absorbent resins (2) and (3) that were the subject of the surface crosslinking treatment exceeded 5% by mass.

[0211] The comparative recycled water absorbent resin (4) described in Comparative Example 7 has excellent CRC and AUL0.3 recovery rates because the 5-minute water soluble component amount of the comparative recovered water absorbent resin (4) before surface crosslinking is 5 mass% or less. However, the 16-hour water soluble component amount of the comparative recovered water absorbent resin (4) before surface crosslinking is very small at 3.5 mass%. Therefore, the recycling rate of the comparative recovered water absorbent resin (4) before surface crosslinking is a low value of less than 80%, and as a result, it is considered that the production amount of the comparative recycled water absorbent resin (4) obtained by surface crosslinking the comparative recovered water absorbent resin (4) in Comparative Example 7 is small. That is, it is considered that the production efficiency of the recycled water absorbent resin is insufficient in Comparative Example 7.

[0212] [Result C: Relationship between 5-minute and 16-hour water-soluble component amounts and AUL0.3 recovery rate] In Example 1 and Comparative Example 5, the 5-minute value and 16-hour value of the amount of water-soluble components of the recovered water absorbent resin (1) and the comparative recycled water absorbent resin precursor (2), as well as the AUL0.3 and AUL0.3 recovery rate of the recycled water absorbent resin (1) and the comparative recycled water absorbent resin (5) are shown in Table 3 below.

[0213] [Table 3]

[0214] As shown in Table 3, the 16-hour water-soluble component amount of the recovered water absorbent resin (1) used in Example 1 was 21.5% by mass, which is a larger value than the 16-hour water-soluble component amount: 18.8% by mass of the comparative recovered water absorbent resin (2) used in Comparative Example 5. The 5-minute water-soluble component amount of the recovered water absorbent resin (1) was 2.9% by mass, which is a smaller value than the 5-minute water-soluble component amount: 5.4% by mass of the comparative recovered water absorbent resin (2), which is the opposite of the 16-hour water-soluble component amount.

[0215] On the other hand, in Example 1, a recycled water absorbent resin (1) is produced by subjecting a recovered water absorbent resin (1) to a surface cross-linking treatment. Similarly, in Comparative Example 5, a comparative recycled water absorbent resin (5) is produced by subjecting a comparative recovered water absorbent resin (2) to a surface cross-linking treatment. The recycled water absorbent resin (1) has an AUL0.3 recovery rate of 94.3%, which is larger than the AUL0.3 recovery rate of the comparative recycled water absorbent resin (5): 54.7%, and is excellent in terms of recovery of absorbency against pressure.

[0216] Therefore, it can be understood that the recovery rate of absorbency under pressure (e.g., AUL0.3 recovery rate, etc.) in the manufacturing method of the recycled water absorbent resin of the present invention is affected only by the amount of 5-minute water soluble component. Therefore, it was found that the manufacturing method of the recycled water absorbent resin of the present invention unexpectedly shows an excellent recovery rate of absorbency under pressure only because the amount of 5-minute water soluble component of the recovered water absorbent resin is a small value of 5 mass% or less, regardless of the amount of 16-hour water soluble component of the recovered water absorbent resin. [Industrial Applicability]

[0217] The method for producing a recycled water-absorbent resin of the present invention can recycle a large amount of water-absorbent resin whose absorbency under pressure has been sufficiently restored from used absorbent articles. Therefore, the method for producing a recycled water-absorbent resin of the present invention can be suitably used in the recycling field for regenerating water-absorbent resin from sanitary materials (sanitary products) such as paper diapers, sanitary napkins, adult incontinence products (incontinence pads), and pet sheets.

Claims

1. A surface cross-linking treatment step is included in which a cross-linked layer is formed on a surface of a recovered water-absorbent resin recovered from a used absorbent article by using a surface cross-linking agent to obtain a reusable water-absorbent resin, The recovered water absorbent resin has a 5-minute water soluble component amount of 5% by mass or less and a 16-hour water soluble component amount of 10% by mass or more relative to the total mass of the recovered water absorbent resin.

2. The method for producing the recycled water absorbent resin according to claim 1, further comprising carrying out a washing step of washing the water absorbent resin separated from the used absorbent article with washing water, and / or a dehydration step of discharging the absorbed liquid, prior to the surface cross-linking treatment step.

3. The method for producing a recycled water absorbent resin according to claim 2, wherein the dehydration treatment step includes contacting the water absorbent resin separated from the used absorbent article with one or more selected from the group consisting of a polyvalent metal salt, an aqueous solution containing a polyvalent metal salt, an acidic liquid, a hydrophilic organic solvent, and an aqueous solution containing a hydrophilic organic solvent.

4. The method for producing a recycled water absorbent resin according to claim 1, wherein a recovery rate of the CRC represented by the following formula (1) is 80% or more. {CRC [g / g] of the reusable water-absorbent resin / CRC [g / g] of the water-absorbent resin contained in the absorbent article before use}×100 (1)

5. The method for producing a recycled water absorbent resin according to claim 1, wherein a recovery rate of AUL0.3 represented by the following formula (2) is 80% or more. {AUL 0.3 [g / g] of the reusable water-absorbent resin / AUL 0.3 [g / g] of the water-absorbent resin contained in the absorbent article before use}×100 (2)

6. The method for producing a recycled water absorbent resin according to claim 1, wherein the recycled water absorbent resin has a recycling rate of 80% or more, which is represented by the following formula (3). Recycling rate (%)=100−(amount of 16-hour water-soluble component of water absorbent resin before recovery operation−amount of 16-hour water-soluble component of recovered water absorbent resin) (3)

Citation Information

Patent Citations

  • Method for separating and recovering pulp component and water absorbing polymer from used absorptive article

    JP2003225645A

  • Regeneration method for water absorbing resin, and water absorbent

    JP2003326161A

  • Method for regenerating highly absorbent polymer, method for producing highly absorbent recycled polymer, and use of alkali metal supply source

    JP2019135046A

  • Method for recycling water absorbent resin

    WO2021162082A1